Photosensitive resin composition, method for manufacturing a polyimide cured film using the same, and polyimide cured film

KR103036477B1Active Publication Date: 2026-10-21ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020247022619
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-05-23
Filing Date
2023-03-30
Publication Date
2026-10-21
Estimated Expiration
2043-03-30

Smart Images

  • Figure 112024073192967-PCT00001
    Figure 112024073192967-PCT00001
  • Figure 112024073192967-PCT00002
    Figure 112024073192967-PCT00002
  • Figure 112024073192967-PCT00003
    Figure 112024073192967-PCT00003
Patent Text Reader

Abstract

According to the present disclosure, a photosensitive resin composition capable of forming a cured relief pattern having low dielectric properties, low curing shrinkage, and good storage stability, reduced phase separation during coating, and high copper adhesion at high resolution is provided, as well as a method for manufacturing a polyimide cured film using the same and a polyimide cured film. The photosensitive resin composition of the present disclosure comprises 100 parts by mass of a copolymer resin comprising polyimide and a polyimide precursor, 0.5 to 30 parts by mass of a photopolymerization initiator, and 100 to 1000 parts by mass of a solvent. The copolymer resin has a polyimide block portion and a polyimide precursor block portion having a specific structure, and the copolymer resin composed of said polyimide and polyimide precursor satisfies 0.10 < n2 / (n2 + n3) < 0.90.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present disclosure relates to a photosensitive resin composition, a method for manufacturing a polyimide cured film using the same, and a polyimide cured film. Background Technology

[0002] Conventionally, polyimide resins, polybenzoxazole resins, phenolic resins, etc., which possess excellent heat resistance, electrical properties, and mechanical properties, are used as insulating materials for electronic components and as passivation films, surface protection films, and interlayer insulating films for semiconductor devices. Among these resins, those provided in the form of photosensitive resin compositions allow for the easy formation of a heat-resistant relief pattern film through ring-closing treatment (imidization, benzoxazoleization) or thermal crosslinking via coating, exposure, development, and curing of the composition. Such photosensitive resin compositions have the characteristic of enabling a significant reduction in process time compared to conventional non-photosensitive materials and are used in the manufacture of semiconductor devices.

[0003] However, semiconductor devices (hereinafter also referred to as "devices") are mounted on printed circuit boards in various ways depending on the purpose. Conventional devices were generally manufactured using the wire bonding method, which involves connecting the external terminals (pads) of the device to the lead frame with thin wires. However, with the acceleration of devices and the operating frequency reaching GHz today, differences in the wiring lengths of each terminal during mounting have reached a point where they affect the operation of the device. Consequently, for the mounting of devices for high-end applications, it has become necessary to accurately control the length of the mounting wiring, and it has become difficult to satisfy this requirement using wire bonding.

[0004] Therefore, flip chip mounting has been proposed, in which a redistribution layer is formed on the surface of a semiconductor chip, bumps (electrodes) are formed thereon, and then the chip is flipped over and directly mounted on a printed circuit board. Since this flip chip mounting allows for precise control of wiring distances, it is being adopted for high-end devices handling high-speed signals, and for mobile phones due to its small mounting size, and demand is rapidly expanding. In addition, recently, a semiconductor chip mounting technology called Fan-Out Wafer Level Package (FOWLP) has been proposed, in which a wafer with a completed front-end process is diced to manufacture a reorganized chip, the reorganized chip is reconstructed on a support and encapsulated with a mold resin, and a redistribution layer is formed after peeling off the support (e.g., Patent Document 1). In Fan-Out Wafer Level Package, since the redistribution layer is formed with a thin film thickness, the height of the package can be reduced, and there are advantages such as high-speed transmission and low cost.

[0005] Recently, accompanied by a significant increase in information and communication volume, there is a need to achieve higher communication speeds than conventional levels. Consequently, a transition to 5th generation communication (5G) using frequencies of 3 GHz or higher, or to communication in the ultra-high frequency bands of the quasi-millimeter wave band (20 GHz to 30 GHz) to the millimeter wave band (30 GHz or higher), where it is easier to secure a wider frequency bandwidth, has become inevitable. As a result, high-frequency compatibility is required not only for printed circuit boards but also for semiconductor chips on which the boards are mounted. Therefore, to reduce transmission loss, an antenna-in-package (AiP) in which a front-end module (FEM) performing radio wave transmission and reception and an antenna are integrated has been developed (see, for example, Patent Document 2 below). In AiP, since the wiring length is short, it is possible to suppress transmission loss that increases in proportion to the wiring length; however, with the increase in communication frequency bands, there is a requirement for low dielectric properties in the rewiring materials. In addition, since AiP requires multiple layers of redistribution layers just like conventional FOWLP, flattening of the redistribution layers is also required.

[0006] As a means to solve the above, in order to reduce transmission loss in the high-frequency band, two main methods can be considered: reducing dielectric loss and reducing conductor loss. Regarding the former, low dielectric properties (low dielectric loss tangent, low dielectric constant) are required for the photosensitive resin composition, and Patent Documents 3, 4, and 5 can be cited as examples. However, in Patent Document 3, the measurement frequency is low at 1 GHz, so it is insufficient as a redistribution layer for AiP used for high-frequency applications. In Patent Document 4, since a polyimide precursor resin and a polyimide resin are blended, there is concern regarding the storage stability of the photosensitive resin composition and phase separation during coating. In Patent Document 5, a partially imidized polyimide precursor is prepared in the varnish by heat-aging a varnish containing a polyimide precursor resin. However, due to the difficulty in controlling the imidization rate, there are challenges regarding uniformity during spin coating, and achieving high resolution is difficult.

[0007] As a means of flattening the redistribution layer, a method of suppressing the curing shrinkage of the redistribution layer can be considered, and Patent Document 6 can be cited as an example. In Patent Document 6, high flattening is achieved by using a polyfunctional (meth)acrylate in a polyimide resin. However, there is no description regarding dielectric properties, and there is concern that dielectric properties may deteriorate at high frequencies due to the influence of a large amount of polyfunctional (meth)acrylate. Prior art literature

[0008] Japanese Published Patent Application No. 2005-167191, U.S. Patent Application Publication No. 2016 / 0104940, Specification International Publication No. 2019 / 044874, Taiwan Publication No. 2020 / 026762, Japanese Published Patent Application No. 2022-54416, Japanese Published Patent Application No. 2021-152634 The problem to be solved

[0009] Recently, as package mounting technology has diversified, the types of supports have become more diverse and the redistribution layer has become more multilayered. Consequently, the influence of the dielectric constant and dielectric loss tangent (tanδ) of the insulating material used for wiring formation has increased. When the dielectric constant or dielectric loss tangent is high, transmission loss increases due to the increase in dielectric loss. While polyimide resins offer high material reliability due to their excellent insulation performance and thermomechanical properties, high dielectric constants and dielectric loss tangents are becoming a problem due to the influence of polar functional groups derived from the imide group, polar functional groups added for photosensitive processes, and additives. Additionally, there are cases where the flatness of the redistribution layer, resulting from low curing shrinkage due to the multilayering of the redistribution layer, becomes a problem.

[0010] The present disclosure aims to provide a photosensitive resin composition capable of forming a cured relief pattern having low dielectric properties, low curing shrinkage, and good storage stability, reduced phase separation during coating, and high copper adhesion at high resolution, a method for manufacturing a polyimide cured film using the same, and a polyimide cured film. means of solving the problem

[0011] Examples of embodiments of the present disclosure are listed in the following items [1] to

[16] .

[0012] [1]

[0013] (A) 100 parts by mass of a copolymer resin comprising a polyimide and a polyimide precursor;

[0014] (B) 0.5 to 30 parts by mass of a photopolymerization initiator and;

[0015] (C) 100 to 1000 parts by mass of solvent; as a photosensitive resin composition comprising,

[0016] The copolymer resin comprising the above polyimide and polyimide precursor has a structure represented by the following general formula (1), and

[0017] [Chemical Formula 1]

[0018]

[0019] In the above formula (1), X1, X2 and X3 are each independently a tetravalent organic group having 6 to 40 carbon atoms, Y1 and Y2 are each independently a divalent organic group having 6 to 40 carbon atoms, n1 is an integer from 2 to 30, n2 and n3 are each independently an integer from 2 to 150, Z3, Z4, Z5, and Z6 are each independently a monovalent organic group, and at least one of Z3, Z4, Z5, and Z6 is a photopolymerizable functional group,

[0020] A photosensitive resin composition comprising the above polyimide and polyimide precursor, satisfying 0.10 < n2 / (n2 + n3) < 0.90.

[0021] [2]

[0022] The above photopolymerizable functional group,

[0023] A photosensitive resin composition described in Item 1, comprising a structure represented by the following general formula (2).

[0024] [Chemical Formula 2]

[0025]

[0026] (In Equation (2), R5, R6, and R7 are each independently a hydrogen atom or a monovalent organic group having 1 to 3 carbon atoms, and m1 is an integer from 2 to 10.)

[0027] [3]

[0028] A photosensitive resin composition described in Item 1 or 2, wherein n2 / (n2+ n3) satisfies 0.40 < n2 / (n2+ n3) < 0.90.

[0029] [4]

[0030] The copolymer resin comprising the above (A) polyimide and polyimide precursor is a photosensitive resin composition described in any one of items 1 to 3, which does not contain halogen atoms.

[0031] [5]

[0032] A photosensitive resin composition described in any one of items 1 to 4, wherein the polyimide of a polyimide cured film obtained by heating and curing the above photosensitive resin composition at 350°C has an imide group concentration U, which is the ratio of the molecular weight of the imide group to the molecular weight of a repeating unit comprising a structure derived from a tetracarboxylic acid dianhydride and a diamine, of 12 wt% to 26 wt%.

[0033] [6]

[0034] X1, X2, and X3 of the copolymer resins comprising the above (A) polyimide and polyimide precursor have a structure represented by the following general formula (4), and

[0035] [Chemical Formula 3]

[0036]

[0037] In formula (4), R8 and R9 are each independently organic groups having 1 to 10 carbon atoms, m2 and m3 are integers selected from 0 to 4, satisfying m2 + m3 ≥ 1, and Z1 is selected from any group consisting of single bonds, organic groups having 1 to 30 carbon atoms, and organic groups containing heteroatoms, * two of which represent bonds to the main chain of the resin, and the other two represent bonds to the side chains in the above general formula (1); also / or,

[0038] Y1 and / or Y2 include a structure represented by the following general formula (7), and

[0039] [Chemical Formula 4]

[0040]

[0041] A photosensitive resin composition described in any one of items 1 to 5, wherein in formula (7), R8 and R9 are each independently organic groups having 1 to 10 carbon atoms, m2 and m3 are integers selected from 0 to 4, satisfying m2 + m3 ≥ 1, Z1 is selected from the group consisting of single bonds, organic groups having 1 to 30 carbon atoms, and organic groups containing heteroatoms, and * means bonded to the main chain of the resin.

[0042] [7]

[0043] A photosensitive resin composition described in any one of items 1 to 6, wherein the copolymer resin comprising the above (A) polyimide and polyimide precursor has other reactive substituents at the resin ends that polymerize by heat or light, which are different from the photopolymerizable functional groups included in the repeating units.

[0044] [8]

[0045] (D) A photosensitive resin composition described in any one of items 1 to 7, further comprising a silane coupling agent.

[0046] [9]

[0047] (E) A photosensitive resin composition described in any one of items 1 to 8, further comprising a radical polymerizable compound.

[0048]

[10]

[0049] (F) A photosensitive resin composition described in any one of items 1 to 9, further comprising a thermal crosslinking agent.

[0050]

[11]

[0051] (G) A photosensitive resin composition described in any one of items 1 to 10, further comprising a filler.

[0052]

[12]

[0053] The following processes (1) ~ (5):

[0054] (1) A process of forming a photosensitive resin layer on a substrate by applying a photosensitive resin composition described in any one of items 1 to 11 onto the substrate;

[0055] (2) A process of heating and drying the obtained photosensitive resin layer;

[0056] (3) Process of exposing a photosensitive resin layer after heating and drying;

[0057] (4) A process for developing a photosensitive resin layer after exposure; and

[0058] (5) A process of heat-treating a photosensitive resin layer after development to form a polyimide cured film; a method for manufacturing a polyimide cured film comprising:

[0059]

[13]

[0060] A method for manufacturing a cured film obtained by applying a resin composition described in any one of items 1 to 11 onto a substrate, followed by photolithography, development, and subsequent heat treatment, wherein the cured film has a dielectric loss tangent of 0.003 to 0.011 measured at 40 GHz using a perturbation-type split cylinder resonance method.

[0061]

[14]

[0062] As a polyimide cured film, the dielectric loss tangent at a frequency of 40 GHz by the perturbation-type split-cylinder resonance technique is 0.003 to 0.011, the RFA is 0.81 to 0.93, and the following formula:

[0063] 85 < RFA / tanδ 40 < 175

[0064] {In the formula, RFA represents the residual film rate (ratio) after heat curing, and tanδ 40 A polyimide cured film satisfying { represents the dielectric loss tangent at a frequency of 40 GHz by the perturbation-type split cylinder resonance technique.}

[0065]

[15]

[0066] A method for manufacturing a copolymer comprising a polyimide and a polyimide precursor, wherein the method comprises the following process:

[0067] (i) obtaining a diamine oligomer having repeating units of a polyimide structure by condensing a first diamine compound with a first tetracarboxylic acid dianhydride or its acid / substituent adduct and imidizing it;

[0068] (ii) condensing the diamine oligomer with a second tetracarboxylic acid dianhydride or its acid / substituent adduct to synthesize a polyimide-imide precursor portion having a polyimide block portion;

[0069] (iii) Synthesizing a polyimide precursor portion by condensing a third tetracarboxylic acid dianhydride or its acid / substituent adduct with a second diamine compound on the polyimide-imide precursor portion, and

[0070] A method for preparing a copolymer, wherein the first tetracarboxylic acid dianhydride, the second tetracarboxylic acid dianhydride, and the third tetracarboxylic acid dianhydride may be the same or different from each other, at least one of the second tetracarboxylic acid dianhydride and the third tetracarboxylic acid dianhydride is in the form of an acid / substituent adduct having a photopolymerizable functional group, and the first diamine compound and the second diamine compound may be the same or different from each other.

[0071]

[16]

[0072] As a method for manufacturing a photosensitive resin composition, the method comprises:

[0073] Manufacturing a copolymer resin comprising a polyimide and a polyimide precursor by the method described in Item 15;

[0074] A method for preparing a photosensitive resin composition, comprising the steps of: (A) mixing 100 parts by mass of a copolymer resin comprising the polyimide and a polyimide precursor, (B) 0.5 to 30 parts by mass of a photopolymerization initiator, and (C) 100 to 1000 parts by mass of a solvent to obtain a photosensitive resin composition. Effects of the invention

[0075] According to the present disclosure, a photosensitive resin composition capable of forming a cured relief pattern having low dielectric properties, low curing shrinkage, and good storage stability, reduced phase separation during coating, and high copper adhesion at high resolution, a method for manufacturing a polyimide cured film using the same, and a polyimide cured film can be provided. Specific details for implementing the invention

[0076] The embodiments of the present disclosure will be described in detail below. Throughout this specification, when structures represented by the same reference numeral in general formulas exist in multiple quantities within a molecule, they are each selected independently unless otherwise specified, and may be identical or different from one another. Furthermore, structures represented by a common reference numeral in different general formulas are also each selected independently unless otherwise specified, and may be identical or different from one another.

[0077] <Photosensitive resin composition>

[0078] The photosensitive resin composition of the present disclosure comprises (A) 100 parts by mass of a copolymer resin comprising a specific polyimide and a polyimide precursor, (B) 0.5 to 30 parts by mass of a photopolymerization initiator, and (C) 100 to 1000 parts by mass of a solvent. Optionally, the photosensitive resin composition of the present disclosure may further comprise, in addition to the above components, (D) a silane coupling agent, (E) a radical polymerizable compound, (F) a thermal crosslinking agent, (G) a filler, and other components.

[0079] (A) Copolymer resin comprising polyimide and polyimide precursor

[0080] A copolymer resin comprising a polyimide and a polyimide precursor (hereinafter also simply referred to as "copolymer resin") preferably comprises a structure represented by the following general formula (1).

[0081] General formula (1) :

[0082] [Chemical Formula 5]

[0083]

[0084] In Formula (1), X1, X2, and X3 are each independently a tetravalent organic group having 6 to 40 carbon atoms, and Y1 and Y2 are each independently a divalent organic group having 6 to 40 carbon atoms. X1, X2, and X3 may be the same or different, and Y1 and Y2 may be the same or different. n1 is an integer from 2 to 30. n2 and n3 are each independently integers from 2 to 150. In the present disclosure, the unit of n1 in Formula (1) is referred to as the "polyimide block portion," the unit of n2 as the "polyimide-imide precursor portion," and the unit of n3 as the "polyimide precursor portion." In formula (1), for simplicity, only one polyimide-imide precursor part and one polyimide precursor part are described, but the copolymer resin may have multiple polyimide-imide precursor parts and multiple polyimide precursor parts randomly distributed among them.

[0085] In Formula (1), Z3, Z4, Z5, and Z6 are each independently monovalent organic groups, provided that at least one of them is a photopolymerizable functional group. The photopolymerizable functional group preferably includes a reactive unsaturated bond that polymerizes by light. It is more preferable that Z3, Z4, Z5, and Z6 form an ester bond (hereinafter referred to as the "ester bond type") or form an amide bond (hereinafter referred to as the "amide bond type") together with the carbonyl group (-C(=O)-) to which they are directly bonded. When Z3, Z4, Z5, and Z6 are side chains of the ester bond type, they can be represented as R1O-, R2O-, R3O-, and R4O-, respectively, and when they are side chains of the amide bond type, they can be represented as R1NH-, R2NH-, R3NH-, and R4NH-, respectively. Z3, Z4, Z5, and Z6 may all be of the ester type, all be of the amide type, or be a combination of the ester type and the amide type.

[0086] In Formula (1), R1, R2, R3, and R4 are each independently a hydrogen atom or a monovalent organic group having 1 to 40 carbon atoms. However, at least one of R1, R2, R3, and R4 is a photopolymerizable functional group, and may be selected from at least one group including (meth)acryloyloxyalkyl group, allyl group, ethynyl group, and styryl group, among others, a (meth)acryloyloxyalkyl group is more preferred. It is even more preferable that Z3, Z4, Z5, and Z6 include a photopolymerizable functional group represented by the following general formula (2).

[0087] General formula (2) :

[0088] [Chemical Formula 6]

[0089]

[0090] In formula (2), R5, R6, and R7 are each independently a hydrogen atom or a monovalent organic group having 1 to 3 carbon atoms, and m1 is an integer from 2 to 10. Examples of monovalent organic groups having 1 to 3 carbon atoms include methyl groups, ethyl groups, n-propyl groups, and isopropyl groups, preferably methyl groups. R5 is preferably a hydrogen atom or a methyl group, and R6 and R7 are preferably a hydrogen atom or a methyl group, more preferably a hydrogen atom. m1 is preferably an integer from 2 to 5, more preferably an integer from 2 to 3. Z3, Z4, Z5, and Z6 are preferably ester bonds represented by R1O-, R2O-, R3O-, and R4O-, amide bonds represented by R1NH-, R2NH-, R3NH-, and R4NH-, or a combination thereof, and R1, R2, R3, and R4 are each independently photopolymerizable functional groups represented by the general formula (2).

[0091] A copolymer resin comprising polyimide and a polyimide precursor satisfies the ratio of the moles of the polyimide-imide precursor portion (n2 units) to the total moles of the polyimide-imide precursor portion (n2 units) and the polyimide precursor portion (n3 units) (hereinafter also referred to as the "imide structure introduction rate") of 0.10 < n2 / (n2 + n3) < 0.90. As a result, a photosensitive resin composition can be obtained in which the polyimide after curing exhibits low dielectric properties and low curing shrinkage, and is capable of forming a cured relief pattern with good storage stability and high resolution.

[0092] By including the structure represented by the above general formula (1), a cured film with good resolution of the relief pattern, low dielectric properties, and low curing shrinkage is obtained. Although not bound by theory, it is thought that the resolution of the relief pattern is improved because the polyimide block portion (unit of n1) and the polyimide precursor structure (i.e., the imide precursor structure in the units of n2 and n3) are contained within the same molecule, and the polyimide-imide precursor portion is present in a specific ratio, thereby suppressing swelling of the exposed area and making it easier to secure contrast with the unexposed area. In addition, it is thought that since a portion of the copolymer resin has a polyimide block portion, the detachment portion of the side chain structure during ring closure is reduced, thereby suppressing curing shrinkage and enabling the expression of low dielectric properties. Furthermore, by having the polyimide block portion and the polyimide precursor structure within the same molecule, the polyimide structure with low solubility can exist stably in the photosensitive resin composition solution (hereinafter also referred to as "varnish"). As a result, it is believed that the storage stability of the varnish is not compromised. On the other hand, when the varnish containing the polyimide precursor resin is heated to form an imide structure, the curing shrinkage increases because photosensitive groups detached from the side chain structure remain in the varnish.

[0093] From the perspective of resolution, low dielectric properties, and low curing shrinkage, the imide structure introduction rate is preferably 0.10 to 0.90. From the perspective of resolution, a lower imide structure introduction rate is preferable, and from the perspective of low dielectric properties and low curing shrinkage, a higher n2 / (n2+n3) is preferable, so the imide structure introduction rate is more preferably 0.20 to 0.90, even more preferably 0.30 to 0.90, even more preferably 0.40 to 0.90, particularly preferably 0.43 to 0.80, and particularly preferably 0.45 to 0.75.

[0094] In terms of resolution, low dielectric properties, and low curing shrinkage, the ratio of the copolymer resin represented by the general formula (1) to the total mass of the copolymer comprising (A) polyimide and polyimide precursor is preferably 25 mass% or more, more preferably 35 mass% or more, more preferably 50 mass% or more, particularly preferably 75 mass% or more, particularly preferably 90 mass% or more, particularly preferably 95 mass% or more, and most preferably 100 mass%.

[0095] In the above general formula (1), n2 is preferably an integer from 3 to 100, more preferably an integer from 5 to 70, in terms of the photosensitive properties and mechanical properties of the photosensitive resin composition. n3 is preferably an integer from 3 to 100, more preferably an integer from 5 to 70, in terms of the photosensitive properties and mechanical properties. n1 is preferably an integer from 2 to 30, more preferably an integer from 5 to 20, in terms of coatability and dielectric loss tangent. The larger n1 is, the higher the introduction rate of the imide structure and the better the dielectric loss tangent. On the other hand, if n1 is excessively large, coatability is impaired, so the balance is important.

[0096] In the above general formula (1), the tetravalent organic group represented by X1, X2, and X3 is preferably an organic group having 6 to 40 carbon atoms in order to achieve both heat resistance and photosensitive properties, and more preferably an aromatic group or an alicyclic aliphatic group in which the -COOR1 group, the -COOR2 group, and the -CONH- group are in ortho positions to each other. As for the tetravalent organic group represented by X1, X2, and X3, specifically, an organic group having 6 to 40 carbon atoms containing an aromatic ring, for example, the following general formula (3):

[0097] [Chemical Formula 7]

[0098]

[0099] {Equation (3), R11 A group having a structure represented by { is a monovalent group selected from the group consisting of a hydrogen atom, a fluorine atom, a C1 to C10 hydrocarbon group, and a C1 to C10 fluorine-containing hydrocarbon group, m5 is an integer from 1 to 2, m6 is an integer from 1 to 3, and m7 is an integer from 1 to 4.} may be used, but is not limited to these. The tetravalent organic groups represented by X1, X2, and X3 may be a single type or a combination of two or more types. X1, X2, and X3 having a structure represented by the above formula (3) are particularly preferred in that they provide both heat resistance and photosensitive properties.

[0100] In the above general formula (1), X1, X2, and X3 preferably include a structure represented by the following general formula (4) in terms of resolution and low dielectric properties.

[0101] General formula (4) :

[0102] [Chemical Formula 8]

[0103]

[0104] {In the formula, R8 and R9 are each independently organic groups having 1 to 10 carbon atoms, m2 and m3 are integers selected from 0 to 4, satisfying m2 + m3 ≥ 1, and Z1 is selected from any group consisting of single bonds, organic groups having 1 to 30 carbon atoms, and organic groups containing heteroatoms. * Two of these represent bonds to the main chain of the resin, and the other two represent bonds to the side chains in the above general formula (1) (i.e., Z3-(C=O)- and Z4-(C=O)-, or Z5-(C=O)- and Z6-(C=O)-).}

[0105] [Chemical Formula 9]

[0106]

[0107] {In the formula, Z2 is selected from the group consisting of single bonds, organic groups having 1 to 30 carbon atoms, and organic groups containing heteroatoms. * Two of these represent bonds to the main chain of the resin, and the other two represent bonds to the side chains in the general formula (1).}

[0108] The organic group having 1 to 10 carbon atoms, represented by R8 and R9 of the above general formula (4), is preferably a straight-chain or branched alkyl group. By introducing an alkyl group into the aromatic ring, the solubility of (A) copolymer resin in the developer is improved, contrast with the exposed area is easily secured, and the resolution of the relief pattern is improved. In addition, by introducing an alkyl group into the aromatic ring, the polarization rate is reduced, resulting in low dielectric properties.

[0109] R8 and R9 of the above general formula (4) are, in terms of chemical resistance, preferably organic groups having 1 to 4 carbon atoms, more preferably alkyl groups having 1 to 4 carbon atoms, examples of which include methyl groups, ethyl groups, propyl groups and butyl groups, and particularly preferably methyl groups.

[0110] Among the above general formulas (1), the structure represented by X1, X2 and X3 is more preferably to include at least one structure selected from the group consisting of the following general formula (5).

[0111] General formula (5) :

[0112] [Chemical Formula 10]

[0113]

[0114] * Two of them represent bonds to the main chain of the resin, and the other two represent bonds to the side chains in the above general formula (1). The structures of X1, X2, and X3 in the above general formula (1) are not limited to the structures exemplified in (3), (4), and (5). The above structures may be of one type or a combination of two or more types.

[0115] In the above general formula (1), the divalent organic groups represented by Y1 and Y2 may be aliphatic chains (alkylene groups) having 6 to 40 carbon atoms, preferably 6 to 20 carbon atoms, for example, heptylene groups, octylene groups, nonylene groups, decylene groups, and undecylene groups; and aromatic groups having 6 to 40 carbon atoms. In terms of achieving both heat resistance and photosensitive properties, they are preferably aromatic groups, more preferably aromatic groups having 6 to 40 carbon atoms, for example, the following general formula (6):

[0116] [Chemical Formula 11]

[0117]

[0118] {Equation (6), R 11 A group having a structure represented by { is a monovalent group selected from the group consisting of a hydrogen atom, a fluorine atom, a C1 to C10 hydrocarbon group, and a C1 to C10 fluorine-containing hydrocarbon group, m6 is an integer from 1 to 3, and m7 is an integer from 1 to 4.} may be used, but is not limited to these. The divalent organic groups represented by Y1 and Y2 may be a single type or a combination of two or more types. Y1 and Y2 groups having a structure represented by the above formula (6) are particularly preferred in that they provide both heat resistance and photosensitive properties.

[0119] In the above general formula (1), Y1 and / or Y2 preferably include a structure represented by the following general formula (7) in terms of resolution and low dielectric properties.

[0120] General formula (7) :

[0121] [Chemical Formula 12]

[0122]

[0123] {In the formula, R8 and R9 are each independently organic groups having 1 to 10 carbon atoms, m2 and m3 are integers selected from 0 to 4, satisfying m2 + m3 ≥ 1, and Z1 is selected from any one of the group consisting of single bonds, organic groups having 1 to 30 carbon atoms, and organic groups containing heteroatoms. * indicates bonding to the main chain of the resin.}

[0124] The organic group having 1 to 10 carbon atoms, represented by R8 and R9 of the above general formula (7), is preferably a straight-chain or branched alkyl group. By introducing an alkyl group into the aromatic ring, the solubility of (A) copolymer resin in the developer is improved, contrast with the exposed area is easily secured, and the resolution of the relief pattern is improved. In addition, by introducing an alkyl group into the aromatic ring, the polarization rate is reduced, resulting in low dielectric properties.

[0125] R8 and R9 of the above general formula (7) are, in terms of chemical resistance, preferably organic groups having 1 to 4 carbon atoms, more preferably alkyl groups having 1 to 4 carbon atoms, examples of which include methyl groups, ethyl groups, propyl groups, and butyl groups, and particularly preferably methyl groups. Examples of the above general formula (7) include at least one structure selected from the group consisting of the following general formula (8).

[0126] General formula (8) :

[0127] [Chemical Formula 13]

[0128]

[0129] * means binding to the main chain of the resin.

[0130] Among the above general formula (1), the structure represented by Y1 and Y2 preferably includes at least one structure selected from the group consisting of the following general formula (9).

[0131] General formula (9) :

[0132] [Chemical Formula 14]

[0133]

[0134] * indicates bonding to the main chain of the resin. The structures of Y1 and Y2 in the above general formula (1) are not limited to the structures exemplified in (6) to (9). The above structures may be one type or a combination of two or more types.

[0135] In the above general formula (1), at least one or all of X1, X2, X3, Y1, and Y2 are preferably not to contain halogen atoms for the purpose of inhibiting copper corrosion in the heat curing process. That is, it is more preferable that (A) copolymer resin is not to contain halogen atoms.

[0136] (A) In the copolymer resin, it is preferable that at least one of X1, X2, and X3, which are backbone components derived from tetracarboxylic acid compounds, and Y1 and Y2, which are backbone components derived from diamine compounds, have two or more benzene rings. The two or more benzene rings may be bonded to each other directly or through an interposed organic group of two or more valences. The number of benzene rings may be three or more, four or more, six or fewer, five or fewer, or four or fewer, and more preferably four. It is further preferable that the total number of carbon atoms constituting X1, X2, and X3, which have structures derived from tetracarboxylic acid compounds, and Y1 and Y2, which have structures derived from diamine compounds, is greater than 39. (A) By having such a structure, the resolution of the negative-type photosensitive resin composition is maintained, and the resulting cured relief pattern tends to have low dielectric properties.

[0137] The photosensitive resin composition of the present disclosure has an imide group concentration U in the polyimide of a polyimide cured film obtained by heating and curing the photosensitive resin composition, which is 12 wt% to 26 wt%. In this specification, "imide group concentration U" refers to the ratio of the molecular weight of the imide group to the molecular weight of the repeating unit containing a structure derived from a tetracarboxylic acid dianhydride and a diamine compound in the polyimide of a polyimide cured film obtained by heating and curing the photosensitive resin composition at 350°C. The condition of heating and curing at 350°C is intended to clarify the standard for the aliphatic hydrocarbon group concentration T by basing it on a state in which (A) the copolymer resin is approximately 100% imidized, and it is not intended that the photosensitive resin composition is heated and cured at 350°C in actual use.

[0138] If the imide group concentration U is 12.0 wt% or higher, the resolution of the relief pattern tends to be good. The imide group concentration U is preferably 15 wt% or higher, and more preferably 17.5 wt% or higher. Meanwhile, the dielectric loss tangent of the polyimide cured film obtained by having an imide group concentration U of 26 wt% or lower tends to be good. The imide group concentration U is more preferably 23.0 wt% or lower, and even more preferably 20.5 wt% or lower.

[0139] The imide group concentration U in the repeating unit of the polyimide cured film is given by the following formula (I), using the molecular weight of the tetracarboxylic acid dianhydride and the molecular weight of the diamine compound used in the preparation of (A) the copolymer resin:

[0140] 70.02 × 2 / [Mw(A) + Mw(B) – 36] × 100 (I)

[0141] {In Formula (I), Mw(A) represents the molecular weight of the tetracarboxylic acid dianhydride, and Mw(B) represents the molecular weight of the diamine.} It is also represented as follows. In addition, when two or more types of tetracarboxylic acid dianhydrides and / or diamine compounds are used, for example, when preparing using two types of tetracarboxylic acid dianhydrides and / or diamines, the following Formula (II):

[0142] 70.02 × 2 / [Mw(A1) × a1+ Mw(A2) × a2+ Mw(B1) × b1+ Mw(B2) × b2- 36] × 100 (II)

[0143] {In formula (II), Mw(A1) represents the molecular weight of the first tetracarboxylic acid dianhydride, Mw(A2) represents the molecular weight of the second tetracarboxylic acid dianhydride, a1 represents the content of the first tetracarboxylic acid dianhydride, a2 represents the content of the second tetracarboxylic acid dianhydride, Mw(B1) represents the molecular weight of the first diamine compound, Mw(B2) represents the molecular weight of the second diamine compound, b1 represents the content of the first diamine compound, and b2 represents the content of the second diamine compound. provided that a1, a2, b1, and b2 each satisfy a1 + a2 = 1 and b1 + b2 = 1.} It is expressed in the same way even when three or more types of tetracarboxylic acid dianhydrides and / or diamines are used. If tetracarboxylic acid and / or tetracarboxylic acid dichloride is used in the raw material, the calculation is performed using the mass of the corresponding tetracarboxylic acid dianhydride.

[0144] (A) The copolymer resin may have other reactive substituents at the ends of the main chain that are crosslinked by heat or light, which are different from the photopolymerizable functional groups included in the repeating units. The reactive substituents at the ends are preferably groups having reactive unsaturated bonds that can react with heat or light to crosslink with each other. (A) The copolymer resin preferably has at least one of the structures represented by the following general formulas (E1) and (E2) at the ends of the main chain. By having these reactive substituents at the ends of the main chain of the (A) copolymer resin, a high-resolution negative-type photosensitive resin composition having improved residual film rate or dielectric properties after curing can be obtained.

[0145] General formula (E1):

[0146] [Chemical Formula 15]

[0147]

[0148] In formula (E1), a1 comprises at least one bond selected from amide, imide, urea, and urethane bonds, b1 is a reactive substituent that crosslinks by heat or light, and e1 is a monovalent organic group having 1 to 30 carbon atoms. R 12 , R 15 is, each independently, a hydrogen atom or a monovalent organic group having 1 to 30 carbon atoms, and R 13 , R 14 Each is, independently, a hydrogen atom, a monovalent or divalent organic group having 1 to 30 carbon atoms, or all of which are parts of an aromatic ring or an aliphatic ring. provided that R 13 and R 14 There is no case where they are all hydrogen atoms, and R 13 and / or R 14 It is connected to the main chain structure.

[0149] General formula (E2):

[0150] [Chemical Formula 16]

[0151]

[0152] In formula (E2), f1 comprises at least one bond among an amide bond, an imide bond, a urea bond, a urethane bond, and an ester bond, g1 is a reactive substituent that is crosslinked by heat or light, and R 16 ~ R 20 Each forms, independently, a hydrogen atom, a monovalent or divalent organic group having 1 to 30 carbon atoms, or an aromatic ring or an aliphatic ring. However, R 17 , R 18 , R 19 There is no case where it simultaneously becomes a hydrogen atom, and R 17 , R 18 and R 19 Any one or two of them are connected to the main chain structure. It is preferable that f1 include at least one group among an amide group, an imide bond, a urea group, and a urethane group, as it is easy to crosslink and has high chemical resistance due to being difficult to hydrolyze.

[0153] The reactive substituent b1, which is crosslinked by heat or light, is preferably at least one selected from, for example, an acrylic group, a methacrylic group, a vinyl group, an alkenyl group, a cycloalkenyl group, an alkadienyl group, a cycloalkadienyl group, a styryl group, an ethynyl group, an imino group, an isocyanato group, a cyanato group, a cycloalkyl group, an epoxy group, an oxetanyl group, a carbonate group, a hydroxyl group, a mercapto group, a methylol group, and an alkoxyalkyl group. For the sake of film thickness uniformity, b1 is preferably at least one selected from an acrylic group, a methacrylic group, a vinyl group, an alkenyl group, a cycloalkenyl group, an alkadienyl group, a cycloalkadienyl group, a styryl group, and an ethynyl group. A methacrylic group is particularly preferred.

[0154] The reactive substituent g1, which is crosslinked by heat or light, is, for example, at least one selected from an acrylic group, a methacrylic group, a vinyl group, an alkenyl group, a cycloalkenyl group, an alkadienyl group, a cycloalkadienyl group, a styryl group, an ethynyl group, an imino group, an isocyanato group, a cyanato group, a cycloalkyl group, an epoxy group, an oxetanyl group, a carbonate group, a hydroxyl group, a mercapto group, a methylol group, and an alkoxyalkyl group. For the sake of film thickness uniformity, it is preferable that g1 is at least one selected from an acrylic group, a methacrylic group, a vinyl group, an alkenyl group, a cycloalkenyl group, an alkadienyl group, a cycloalkadienyl group, a styryl group, and an ethynyl group. A methacrylic group is particularly preferred for g1.

[0155] Specific examples of a compound having a reactive substituent that reacts with heat or light and a site that also reacts with a carboxyl group, and a main chain end of a polyimide precursor modified with a reactive substituent are shown below.

[0156] [Chemical Formula 17]

[0157]

[0158] (A) Method for preparing a copolymer comprising polyimide and a polyimide precursor

[0159] A method for manufacturing a copolymer comprising a polyimide and a polyimide precursor according to the present disclosure comprises the following process:

[0160] (i) obtaining a diamine oligomer having repeating units of a polyimide structure by condensing a first diamine compound with a first tetracarboxylic acid dianhydride or its acid / substituent adduct and imidizing it;

[0161] (ii) condensing the diamine oligomer with a second tetracarboxylic acid dianhydride or its acid / substituent adduct to synthesize a polyimide-imide precursor portion having a polyimide block portion;

[0162] (iii) Synthesize a polyimide precursor portion by condensing a third tetracarboxylic acid dianhydride or its acid / substituent adduct with a second diamine compound on the polyimide-imide precursor portion. The first tetracarboxylic acid dianhydride, the second tetracarboxylic acid dianhydride, and the third tetracarboxylic acid dianhydride may be the same or different from each other, and at least one of the second tetracarboxylic acid dianhydride and the third tetracarboxylic acid dianhydride is in the form of an acid / substituent adduct having a photopolymerizable functional group, and the first diamine compound and the second diamine compound may be the same or different from each other.

[0163] (Preparation of acid / substituent adducts)

[0164] The first, second, and third tetracarboxylic acid dianhydrides used in processes (i), (ii), and (iii) may be in the form of acid dianhydrides, or in the form having an acid portion (HO-C(=O)-) and a substituent portion (ZC(=O)-, where Z corresponds to Z3 to Z6 of general formula (1)) in which a side chain substituent is pre-added to the acid dianhydride (also referred to as an "acid / substituent adduct" in this disclosure). However, at least one of the second and third tetracarboxylic acid dianhydrides is in the form of an acid / substituent adduct having a photopolymerizable functional group. Z3, Z4, Z5, and Z6 may be of the ester-linked type (hereinafter also referred to as "acid / ester body") or the amide-linked type (hereinafter also referred to as "acid / amide body") as described above, and by using such acid / ester body or acid / amide body, an ester-linked or amide-linked polyimide precursor can be prepared. Tetracarboxylic acid dianhydrides having a tetravalent organic group X1 having 6 to 40 carbon atoms, which are preferably used to prepare ester-linked or amide-linked polyimide precursors, are not limited to tetracarboxylic acid dianhydrides derived from structures exemplified above, but include, for example, pyromellitic anhydride, diphenyl ether-3,3',4,4'-tetracarboxylic acid dianhydride, benzophenone-3,3',4,4'-tetracarboxylic acid dianhydride, biphenyl-3,3',4,4'-tetracarboxylic acid dianhydride, diphenylsulfone-3,3',4,4'-tetracarboxylic acid dianhydride, diphenylmethane-3,3',4,4'-tetracarboxylic acid dianhydride, 2,2-bis(3,4-phthalic anhydride)propane, and 2,2-bis(3,4-anhydride Examples include phthalic acid)-1,1,1,3,3,3-hexafluoropropane, 4,4'-(4,4'-isopropylidenediphenoxy) phthalic anhydride, 4,4'-bis(3,4-dicarboxyphenoxy)benzophenone diacid anhydride, etc. Tetracarboxylic acid dianhydrides may be used alone or in a mixture of two or more types.

[0165] Tetracarboxylic acid dianhydrides containing the tetravalent organic group X1 having 6 to 40 carbon atoms can be reacted with a compound having a photoreactive substituent (photopolymerizable functional group) (also referred to as a “substituent introduction compound” in this disclosure) to obtain an esterified or amidated tetracarboxylic acid (acid / esterified or acid / amid). In addition, the reactive substituent can be introduced to the end of the main chain of (A) copolymer using the above substituent introduction compound. The order of the reaction varies depending on the introduction method.

[0166] Examples of substituent-introducing compounds (also referred to as “first substituent-introducing compounds” in this disclosure) that are preferably used in the synthesis of esterified tetracarboxylic acids (acids / esters) include alcohols having photopolymerizable functional groups. Alcohols having photopolymerizable functional groups are preferably alcohols comprising the structure of general formula (2), for example, 2-hydroxyethyl methacrylate (HEMA), 2-acryloyloxyethyl alcohol, 1-acryloyloxy-3-propyl alcohol, 2-acrylamide ethyl alcohol, methylol vinyl ketone, 2-hydroxyethyl vinyl ketone, 2-hydroxy-3-methoxypropyl acrylate, 2-hydroxy-3-butoxypropyl acrylate, 2-hydroxy-3-phenoxypropyl acrylate, 2-hydroxy-3-butoxypropyl acrylate, 2-hydroxy-3-t-butoxypropyl acrylate, 2-hydroxy-3-cyclohexyloxypropyl acrylate, 2-methacryloyloxyethyl alcohol, Examples include 1-methacryloyloxy-3-propyl alcohol, 2-methacrylamide ethyl alcohol, 2-hydroxy-3-methoxypropyl methacrylate, 2-hydroxy-3-butoxypropyl methacrylate, 2-hydroxy-3-phenoxypropyl methacrylate, 2-hydroxy-3-butoxypropyl methacrylate, 2-hydroxy-3-t-butoxypropyl methacrylate, and 2-hydroxy-3-cyclohexyloxypropyl methacrylate.

[0167] In addition to the above-mentioned alcohols having photopolymerizable functional groups, saturated aliphatic alcohols having 1 to 4 carbon atoms are optionally used. Specific examples thereof include, for instance, methanol, ethanol, n-propanol, isopropanol, n-butanol, tert-butanol, etc.

[0168] Examples of substituent-introducing compounds (also referred to as “first substituent-introducing compounds” in this disclosure) that are preferably used in the synthesis of amidated tetracarboxylic acids (acids / amides) include amines having photopolymerizable functional groups. Examples of amines having photopolymerizable functional groups include, preferably, amines having the structure of general formula (2), such as 2-aminoethyl methacrylate, 2-aminoethyl acrylate, 2-(tert-butylamino)ethyl methacrylate.

[0169] By stirring and mixing the above tetracarboxylic acid dianhydride and the first substituent-introduced compound for 4 to 10 hours at a temperature of 20 to 50 °C in the presence of a basic catalyst such as pyridine, preferably in a suitable reaction solvent, the addition of a substituent to the acid anhydride (e.g., esterification or amidation reaction) is carried out, and a desired acid / substituent adduct can be obtained.

[0170] The reaction solvent is preferably one that completely dissolves the raw material tetracarboxylic acid dianhydride, the compound with the first substituent introduced, and the product acid / substituent adduct. More preferably, it is a solvent that also completely dissolves the polyimide precursor, which is the amide polycondensation product of the acid / substituent adduct and the diamine. Examples include N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, tetramethylurea, ketones, esters, lactones, ethers, halogenated hydrocarbons, hydrocarbons, etc. Specific examples of these include ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc. Examples of esters include methyl acetate, ethyl acetate, butyl acetate, diethyl oxalate, etc. Examples of lactones include γ-butyrolactone. Examples of ethers include ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, etc. Examples of halogenated hydrocarbons include dichloromethane, 1,2-dichloroethane, 1,4-dichlorobutane, chlorobenzene, o-dichlorobenzene, etc. Examples of hydrocarbons include hexane, heptane, benzene, toluene, xylene, etc. These may be used individually or in a mixture of two or more types as needed.

[0171] (Preparation of diamine oligomers)

[0172] Process (i) :

[0173] A diamine oligomer having repeating units of a polyimide structure can be obtained by condensing a first diamine compound with a first tetracarboxylic acid dianhydride or its acid / substituent adduct and then imidizing it. The first tetracarboxylic acid dianhydride used in the condensation reaction is preferably in the form of an acid dianhydride rather than an acid / substituent adduct, from the viewpoint of increasing the imide ring-closing rate. For example, a first tetracarboxylic acid dianhydride containing a tetravalent organic group X1 having 6 to 40 carbon atoms can be condensed with an excess amount of a first diamine compound containing a divalent organic group Y1 having 6 to 40 carbon atoms to achieve heat-closing. The conditions for imidization are not limited, but, for example, heating at 160°C or higher and 300°C or lower for 1 to 10 hours is sufficient. The higher the imide closing rate, the more desirable it is, but not limited to, 90% or more, 95% or more is desirable, and 99% or more or 100% is more desirable.

[0174] As a first diamine compound having a divalent organic group Y1 having 6 to 40 carbon atoms, which is a raw material for a diamine oligomer having a polyimide structure, examples include a diamine having an aliphatic chain (alkylene group) having 6 to 40 carbon atoms, preferably 6 to 20 carbon atoms, such as 1,7-diaminoheptane, 1,10-diaminodecane, 1,11-diaminoundecane, and 1,12-diaminododecane; and a diamine having an aromatic group having 6 to 40 carbon atoms.As diamines having aromatic groups, in addition to diamines derived from structures exemplified above, for example, p-phenylenediamine, m-phenylenediamine, 4,4-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfide, 4,4'-diaminodiphenylsulfone, 3,4'-diaminodiphenylsulfone, 3,3'-diaminodiphenylsulfone, 4,4'-diaminobiphenyl, 3,4'-diaminobiphenyl, 3,3'-diaminobiphenyl, 4,4'-diaminobenzophenone, 3,4'-diaminobenzophenone, 3,3'-diaminobenzophenone, 4,4'-diaminodiphenylmethane, 3,4'-Diaminodiphenylmethane, 3,3'-Diaminodiphenylmethane, 1,4-Bis(4-aminophenoxy)benzene, 1,3-Bis(4-aminophenoxy)benzene, 1,3-Bis(3-aminophenoxy)benzene, Bis[4-(4-aminophenoxy)phenyl]sulfone, Bis[4-(3-aminophenoxy)phenyl]sulfone, 4,4-Bis(4-aminophenoxy)biphenyl, 4,4-Bis(3-aminophenoxy)biphenyl, Bis[4-(4-aminophenoxy)phenyl]ether, Bis[4-(3-aminophenoxy)phenyl]ether, 1,4-Bis(4-aminophenyl)benzene, 1,3-Bis(4-aminophenyl)benzene, 9,10-Bis(4-aminophenyl)anthracene, 2,2-Bis(4-aminophenyl)propane, Examples include 2,2-bis(4-aminophenyl)hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 1,4-bis(3-aminopropyldimethylsilyl)benzene, ortho-tolidinesulfone, 9,9-bis(4-aminophenyl)fluorene, and bis{4-(4-aminophenoxy)phenyl}ketone, and those in which some of the hydrogen atoms on the benzene ring of these are substituted with alkyl chains such as methyl groups or ethyl groups, for example, 2,2'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethoxy-4,4'-diaminobiphenyl, 3,3'-dichloro-4,4'-diaminobiphenyl, and mixtures thereof. However, diamine compounds are not limited to these.These diamine compounds may be used alone or in a mixture of two or more. These diamine compounds may also be used as a second diamine compound.

[0175] (Preparation of a copolymer comprising a polyimide and a polyimide precursor)

[0176] Process (ii):

[0177] A polyimide-imide precursor portion (n2 unit) having a polyimide block portion (n1 unit) can be synthesized by condensing the second tetracarboxylic acid dianhydride or its acid / substituent adduct with the diamine oligomer obtained above as the diamine. The second tetracarboxylic acid dianhydride is preferably in the form of an acid / substituent adduct having a photopolymerizable functional group. The acid / substituent adduct is typically in a solution state dissolved in a reaction solvent after preparing the acid / substituent adduct by the above method. Preferably, the acid / substituent adduct is converted into a polyacid anhydride by adding and mixing a suitable dehydrating condensation agent under ice cooling. Subsequently, a solvent in which the diamine oligomer obtained above is dissolved or dispersed is added dropwise to this, and the two are polycondensed with an amide to obtain a polyimide-imide precursor portion (n2 unit). Diaminosiloxanes may be used in combination with the diamines having the above-mentioned divalent organic group Y1, which serve as raw materials for a diamine oligomer having a polyimide structure. Examples of the above-mentioned dehydration condensation agents include dicyclohexylcarbodiimide (DCC), 1-ethoxycarbonyl-2-ethoxy-1,2-dihydroquinoline, 1,1-carbonyldioxy-di-1,2,3-benzotriazole, N,N'-disuccinimidylcarbonate, etc. As described above, the intermediate polyacid anhydride is obtained.

[0178] Process (iii) :

[0179] A polyimide precursor portion (n3 unit) can be synthesized by further condensing a third tetracarboxylic acid dianhydride or its acid / substituent adduct with a second diamine compound on the obtained polyimide-imide precursor portion. If the second tetracarboxylic acid dianhydride (or its acid / substituent adduct) and the third tetracarboxylic acid dianhydride (or its acid / substituent adduct) are identical, the excess amount of the second tetracarboxylic acid dianhydride (or its acid / substituent adduct) present in the reaction solvent after the synthesis of the polyimide-imide precursor portion may be used as the third tetracarboxylic acid dianhydride (or its acid / substituent adduct). A desired tetracarboxylic acid dianhydride (or its acid / substituent adduct) may be added to the system. If the first diamine compound and the second diamine compound are identical, the excess amount of the first diamine compound present in the reaction solvent after the synthesis of the diamine oligomer may be used as the second diamine compound. The desired diamine compound may also be added to the system.

[0180] (Reactive resin end formation)

[0181] By the following method, a different reactive substituent that polymerizes by heat or light, which is different from the photopolymerizable functional group included in the repeating unit of (A) copolymer, can be introduced at the end of the main chain.

[0182] (1) to prepare an acid / substituent adduct having a photopolymerizable functional group and a reactive substituent by reacting a second and / or third tetracarboxylic acid dianhydride with a first substituent-introducing compound having a photopolymerizable functional group, and then reacting a second substituent-introducing compound having a reactive substituent that reacts with heat or light different from that of the first substituent-introducing compound, or to obtain an acid / substituent adduct having a photopolymerizable functional group and a reactive substituent by reacting the second and / or third tetracarboxylic acid dianhydride with the second substituent-introducing compound, and then reacting the first substituent-introducing compound; and / or

[0183] (2) Preparing a diamine oligomer having a second reactive substituent by reacting a diamine oligomer with a compound introducing a second substituent;

[0184] (3) By using the acid / substituent adduct having the photopolymerizable functional group and reactive substituent obtained in (1) above, and / or the diamine oligomer having the reactive substituent obtained in (2) above, the reactive substituent derived from the second substituent-introducing compound can be introduced to the acid end and / or amine end of the main chain of the copolymer (A).

[0185] As for the compound introducing the second substituent, it is preferable that it be a compound introducing the structure represented by the general formulas (E1) and (E2) above. Examples include, but are not limited to, 2-isocyanatoethylacrylate, 2-isocyanatoethylmethacrylate, 2-(2-methacryloyloxyethyloxy)ethylisocyanate, 1,1-(bisacryloyloxymethyl)ethylisocyanate, allylamine, and methacrylic acid chloride.

[0186] In order to improve the adhesion between the photosensitive resin layer formed on the substrate and various substrates by applying a photosensitive resin composition on the substrate, (A) when preparing a copolymer comprising polyimide and a polyimide precursor, diaminosiloxanes such as 1,3-bis(3-aminopropyl)tetramethyldisiloxane and 1,3-bis(3-aminopropyl)tetraphenyldisiloxane may be copolymerized.

[0187] After the amide polycondensation reaction is completed, the by-products of the dehydration condensation agent that coexist in the reaction solution are separated by filtration as needed, and then a suitable solvent, such as water, an aliphatic lower alcohol, or a mixture thereof, is introduced into a solution containing the polymer component to precipitate the polymer component. Additionally, if necessary, operations such as redissolution and redeposition are repeated to purify the polymer, and then vacuum drying is performed to isolate the copolymer containing the desired polyimide and polyimide precursor. To improve the degree of purification, the solution of the polymer may be passed through a column packed with anion and / or cation exchange resin swollen with a suitable organic solvent to remove ionic impurities.

[0188] (A) The weight average molecular weight of a copolymer containing polyimide and a polyimide precursor is preferably 8,000 to 150,000 when measured as the polystyrene equivalent weight average molecular weight by gel permeation chromatography (GPC) in terms of the heat resistance and mechanical properties of the film obtained after heat treatment, more preferably 9,000 to 50,000, and particularly preferably 18,000 to 40,000. A weight average molecular weight of 8,000 or more is preferred because the mechanical properties are good, while a weight average molecular weight of 150,000 or less is preferred because the dispersibility with respect to the developer and the resolution performance of the relief pattern are good. Tetrahydrofuran and N-methyl-2-pyrrolidone are recommended as the developing solvents for gel permeation chromatography. In addition, the molecular weight is determined from a calibration curve prepared using standard monodisperse polystyrene. As for the standard monodisperse polystyrene, it is recommended to select from the organic solvent-based standard sample STANDARD SM-105 manufactured by Showa Denko.

[0189] (B) Photopolymerization initiator

[0190] (B) A photopolymerization initiator is a compound that generates radicals by an active light and can polymerize compounds containing ethylenically unsaturated groups. Examples of initiators that generate radicals by an active light include compounds containing structures such as benzophenone, N-alkylaminoacetophenone, oxime esters, acridine, and phosphine oxide. Examples include aromatic ketones such as benzophenone, N,N,N',N'-tetramethyl-4,4'-diaminobenzophenone (Michler ketone), N,N,N',N'-tetraethyl-4,4'-diaminobenzophenone, 4-methoxy-4'-dimethylaminobenzophenone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1,2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-propanone-1, acrylated benzophenone, and 4-benzoyl-4'-methyldiphenylsulfide; benzoin ether compounds such as benzoin methyl ether, benzoin ethyl ether, and benzoin phenyl ether; and benzoin compounds such as benzoin, methylbenzoin, and ethylbenzoin. 1,2-Octanedione, 1-[4-(phenylthio)-,2-(O-benzoyloxime)], Ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-,1-(O-acetyloxime) (Manufactured by BASF Japan, Inc., Irgacure Oxe02), 1-[4-(phenylthio)phenyl]-3-cyclopentylpropane-1,2-dione-2-(o-benzoyloxime) (Manufactured by Changzhou Powerful Electronic Materials Co., Ltd., PBG305), 1,2-Propanedione, 3-cyclohexyl-1-[9-ethyl-6-(2-furanylcarbonyl)-9H-carbazole-3-yl]-,2-(O-acetyloxime) (TR-PBG-326 manufactured by Nikko Chemtech Co., Ltd., Examples include oxime ester compounds such as (product name); benzyl derivatives such as benzyldimethylketal; acridine derivatives such as 9-phenylacridine, 1,7-bis(9,9'-acridinyl)heptane; N-phenylglycine derivatives such as N-phenylglycine; coumarin compounds; oxazole compounds; and phosphine oxide compounds such as 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, but are not limited to these.The polymerization initiator (C) described above may be used alone or in a mixture of two or more types. Among the photopolymerization initiators, oxime ester compounds are more preferred, particularly in terms of resolution.

[0191] The amount of photopolymerization initiator is 0.5 parts by mass or more and 30 parts by mass or less, with respect to 100 parts by mass of (A) a copolymer comprising a polyimide and a polyimide precursor, and preferably 3 parts by mass or more and 15 parts by mass or less. The above amount is preferably 0.5 parts by mass or more in terms of light sensitivity or patternability, and 30 parts by mass or less in terms of the physical properties of the photosensitive resin layer after curing of the photosensitive resin composition.

[0192] (C) Solvent

[0193] (C) The solvent is not limited to any solvent capable of uniformly dissolving or suspending (A) a copolymer containing a polyimide and a polyimide precursor, and (B) a photopolymerization initiator. Examples of such solvents include γ-butyrolactone, dimethyl sulfoxide, tetrahydrofurfuryl alcohol, ethyl acetoacetate, N,N-dimethylacetoacetamide, ε-caprolactone, 1,3-dimethyl-2-imidazolidinone, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, N,N-dimethylformamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N,N-dimethylacetamide, etc. These solvents may be used individually or in combination of two or more types.

[0194] The above solvent may be used in a range of, for example, 30 to 1,500 parts by mass, preferably 100 to 1,000 parts by mass, per 100 parts by mass of a copolymer comprising (A) a polyimide and a polyimide precursor, depending on the desired coating film thickness and viscosity of the photosensitive resin composition. When the solvent contains an alcohol that does not have an olefinic double bond, the content of the alcohol that does not have an olefinic double bond in the total solvent is preferably 5 to 50 mass%, and more preferably 10 to 30 mass%. When the content of the alcohol that does not have an olefinic double bond is 5 mass% or more, the storage stability of the photosensitive resin composition is improved, and when it is 50 mass% or less, the solubility of the copolymer comprising (A) a polyimide and a polyimide precursor is improved.

[0195] (D) Silane coupling agent

[0196] To improve the adhesion of the relief pattern, the photosensitive resin composition may optionally include (D) a silane coupling agent. (D) The silane coupling agent preferably has a structure represented by the following general formula (9).

[0197] General formula (9) :

[0198] [Chemical Formula 18]

[0199]

[0200] In Equation (9), R 21 is at least one selected from the group consisting of substituents including epoxy groups, phenylamino groups, and ureid groups, and R 22 Each is independently an alkyl group having 1 to 4 carbon atoms, and R 23 is a hydroxyl group or an alkyl group having 1 to 4 carbon atoms, d is an integer from 1 to 3, and m4 is an integer from 1 to 6.

[0201] In general formula (9), d is not limited to an integer from 1 to 3, but 2 or 3 is preferred from the perspective of adhesion to the metal redistribution layer, and 3 is more preferred. m4 is not limited to an integer from 1 to 6, but 1 or more and 4 or less is preferred from the perspective of adhesion to the metal redistribution layer. 2 or more and 5 or less is preferred from the perspective of formability.

[0202] R 21 The substituent is not limited to any structure comprising silver, epoxy groups, phenylamino groups, urea groups, isocyanate groups, and isocyanul groups. Among these, from the perspective of developability or adhesion of the metal redistribution layer, it is preferable to select at least one type from the group consisting of substituents comprising phenylamino groups and substituents comprising urea groups, and substituents comprising phenylamino groups are more preferable. R 22 is not limited to alkyl groups having 1 to 4 carbon atoms. Examples include methyl groups, ethyl groups, propyl groups, isopropyl groups, butyl groups, isobutyl groups, t-butyl groups, etc. R 23 It is not limited to being a hydroxyl group, or an alkyl group having 1 to 4 carbon atoms. As for the alkyl group having 1 to 4 carbon atoms, R 22 An alkyl group identical to can be exemplified.

[0203] Examples of silane coupling agents containing epoxy groups include 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, etc. Examples of silane coupling agents containing phenylamino groups include N-phenyl-3-aminopropyltrimethoxysilane. Examples of silane coupling agents containing ureid groups include 3-ureidopropyltrialkoxysilane. Examples of silane coupling agents containing isocyanate groups include 3-isocyanatepropyltriethoxysilane.

[0204] The content of (D) silane coupling in the resin composition is 0.2 mass% to 10 mass% with respect to 100 mass parts of a copolymer comprising (A) polyimide and a polyimide precursor, and is more preferably 1 mass% to 8 mass% from the perspective of copper adhesion, and even more preferably 2 mass% to 6 mass%.

[0205] (E) Radical polymerizable compounds

[0206] To improve the resolution of the relief pattern and suppress curing shrinkage during heat curing, the photosensitive resin composition may optionally include (E) a radical polymerizable compound. As such compounds, (meth)acrylic compounds that undergo a radical polymerization reaction by a photopolymerization initiator are preferred, and are particularly, but not limited to, diethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, di(meth)acrylates of ethylene glycol or polyethylene glycol, di(meth)acrylates of propylene glycol or polypropylene glycol, di(meth)acrylates or tri(meth)acrylates of glycerol, cyclohexanedi(meth)acrylates, di(meth)acrylates of 1,4-butanediol, di(meth)acrylates of 1,6-hexanediol, di(meth)acrylates of neopentyl glycol, di(meth)acrylates of bisphenol A, (meth)acrylamides, derivatives thereof, trimethylolpropane tri(meth)acrylates, di(meth)acrylates of glycerol, or Examples of compounds include tri(meth)acrylates, di(meth)acrylates of pentaerythritol, tri(meth)acrylates or tetra(meth)acrylates, and ethylene oxide or propylene oxide adducts of these compounds. Among these radical polymerizable compounds, it is preferable to have three or more radical polymerizable groups from the perspective of inhibiting curing shrinkage. In addition, these monomers may be used as a single type or as a mixture of two or more types.

[0207] The content of (E) radical polymerizable compound in the resin composition is 0.5 mass% to 50 mass% with respect to 100 mass parts of a copolymer comprising (A) polyimide and a polyimide precursor, and is more preferably 5 mass% to 40 mass% and even more preferably 10 mass% to 30 mass% from the perspective of resolution and inhibition of curing shrinkage.

[0208] (F) Thermal crosslinking agent

[0209] To suppress curing shrinkage of the film after curing, the photosensitive resin composition may optionally include (F) a thermal crosslinking agent.

[0210] (F) A thermal crosslinking agent refers to a compound that causes an addition reaction or a condensation polymerization reaction by heat. These reactions occur in combinations of (A) a copolymer resin containing a polyimide and a polyimide precursor, (F) a thermal crosslinking agent, (F) thermal crosslinking agents with each other, and (F) a thermal crosslinking agent with other components described below, and the reaction temperature is preferably 150°C or higher.

[0211] (F) Examples of thermal crosslinking agents include alkoxymethyl compounds, epoxy compounds, oxetane compounds, bismaleimide compounds, allyl compounds, and block isocyanate compounds. For the purpose of inhibiting curing shrinkage, it is preferable that the (F) thermal crosslinking agent contains a nitrogen atom.

[0212] Examples of alkoxymethyl compounds include, but are not limited to, the following compounds.

[0213] [Chemical Formula 19]

[0214]

[0215] [Chemical Formula 20]

[0216]

[0217] Examples of epoxy compounds include epoxy compounds containing a bisphenol A type group or hydrogenated bisphenol A diglycidyl ether (e.g., Epolite 4000 manufactured by Kyoei Chemical Co., Ltd.). Oxetane compounds include 1,4-bis{[(3-ethyl-3-oxetanyl)methoxy]methyl}benzene, bis[1-ethyl(3-oxetanyl)]methyl ether, 4,4'-bis[(3-ethyl-3-oxetanyl)methyl]biphenyl, 4,4'-bis(3-ethyl-3-oxetanylmethoxy)biphenyl, ethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, diethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, bis(3-ethyl-3-oxetanylmethyl)diphenoate, trimethylolpropane tris(3-ethyl-3-oxetanylmethyl)ether, pentaerythritol tetrakis(3-ethyl-3-oxetanylmethyl)ether, and poly[[3-[(3-ethyl-3-oxetanyl)methoxy]propyl]silsesquioxane] derivatives, Examples include oxetanyl silicate, phenol novolak-type oxetane, 1,3-bis[(3-ethyloxetane-3-yl)methoxy]benzene, OXT121 (manufactured by Toa Synthetic, trade name), OXT221 (manufactured by Toa Synthetic, trade name), etc. Bis-maleimide compounds include 1,2-bis(maleimide)ethane, 1,3-bis(maleimide)propane, 1,4-bis(maleimide)butane, 1,5-bis(maleimide)pentane, 1,6-bis(maleimide)hexane, 2,2,4-trimethyl-1,6-bis(maleimide)hexane, N,N'-1,3-phenylenebis(maleimide), 4-methyl-N,N'-1,3-phenylenebis(maleimide), N,N'-1,4-phenylenebis(maleimide), 3-methyl-N,N'-1,4-phenylenebis(maleimide), 4,4'-bis(maleimide)diphenylmethane, 3,3'-diethyl-5,5'-dimethyl-4,4'-bis(maleimide)diphenylmethane, or Examples include 2,2-bis[4-(4-maleimidephenoxy)phenyl]propane.Examples of allyl compounds include allyl alcohol, allyl anisole, allyl benzoate ester, allyl cinnamate ester, N-allyloxyphthalimide, allylphenol, allylphenylsulfone, allyl urea, diallyl phthalate, diallyl isophthalate, diallyl terephthalate, diallyl maleate, diallyl isocyanurate, trialylamine, trialyl isocyanurate, trialyl cyanurate, trialylamine, 1,3,5-benzenetricarboxylate, trialyl trimellitate, trialyl phosphate, trialyl phosphite, trialyl citrate, and others. Block isocyanate compounds include hexamethylene diisocyanate-based block isocyanates (e.g., Duranate SBN-70D, SBB-70P, SBF-70E, TPA-B80E, 17B-60P, MF-B60B, E402-B80B, MF-K60B, and WM44-L70G manufactured by Asahi Chemicals Co., Ltd., Takenate B-882N manufactured by Mitsui Chemicals Co., Ltd., 7960, 7961, 7982, 7991, and 7992 manufactured by Baxenden, etc.), tolylene diisocyanate-based block isocyanates (e.g., Takenate B-830 manufactured by Mitsui Chemicals Co., Ltd.), and 4,4'-diphenylmethane diisocyanate-based block isocyanates (e.g., manufactured by Mitsui Chemicals Co., Ltd. Examples include Takenate B-815N, Blanate PMD-OA01 and PMD-MA01 manufactured by Daiei Sangyo Co., Ltd., 1,3-bis(isocyanatemethyl)cyclohexane-based block isocyanates (e.g., Takenate B-846N manufactured by Mitsui Chemicals Co., Ltd., Blanate BI-301, 2507, and 2554 manufactured by Tosho Corporation, etc.), and isophorone diisocyanate-based block isocyanates (e.g., 7950, 7951, and 7990 manufactured by Baxenden Co., Ltd.). Among these, block isocyanates or bismaleimide compounds are preferred from the perspective of storage stability. (F) The thermal crosslinking agent may be used alone or in combination of two or more types.

[0218] The content of (F) thermal crosslinking agent in the resin composition is 0.2 mass% to 40 mass% with respect to 100 mass parts of a copolymer comprising (A) polyimide and a polyimide precursor, and is more preferably 1 mass% to 20 mass% and even more preferably 2 mass% to 10 mass% for low dielectric properties and inhibition of curing shrinkage.

[0219] (G) Filler

[0220] To suppress curing shrinkage of the film after curing, the photosensitive resin composition may optionally include (G) a filler. The filler is not limited to any inert material added to improve strength or various properties.

[0221] It is preferable that the filler be in the form of particles to suppress the increase in viscosity when used in a resin composition. Examples of particles include needle-shaped, plate-shaped, and spherical shapes, but it is preferable that the filler be spherical to suppress the increase in viscosity when used in a resin composition.

[0222] Examples of needle fillers include wollastonite, potassium titanate, zonotlite, aluminum borate, and needle calcium carbonate.

[0223] Examples of plate-shaped fillers include talc, mica, sericite, glass flakes, montmorillonite, boron nitride, and plate-shaped calcium carbonate.

[0224] Examples of spherical fillers include calcium carbonate, silica, alumina, titanium oxide, clay, hydrotalcite, magnesium hydroxide, zinc oxide, and barium titanate. Among these, silica, alumina, titanium oxide, and barium titanate are preferred from the perspective of electrical properties and storage stability when used in a resin composition, and silica and alumina are more preferred.

[0225] Regarding the size of the filler, the primary particle diameter is defined as the size in the case of spherical shapes, and the length of the long side is defined as the size in the case of plate-shaped or needle-shaped shapes; 5 nm to 1000 nm is preferred, and 10 nm to 1000 nm is more preferred. If it is 10 nm or larger, it tends to become sufficiently uniform when used in a resin composition, and if it is 1000 nm or smaller, it can impart photosensitivity. From the perspective of imparting photosensitivity, 800 nm or smaller is preferred, 600 nm or smaller is more preferred, and 300 nm or smaller is particularly preferred. From the perspective of adhesion or uniformity of the resin composition, 15 nm or larger is preferred, 30 nm or larger is more preferred, and 50 nm or larger is particularly preferred.

[0226] The content of (G) filler in the resin composition is 1 vol% to 20 vol% with respect to 100 parts by mass of a copolymer comprising (A) polyimide and a polyimide precursor, and is preferably 5 vol% to 20 vol% from the perspective of dielectric properties, and more preferably 5 vol% to 10 vol% from the perspective of resolution.

[0227] (H) Other components

[0228] The photosensitive resin composition may additionally contain components other than the above (A) to (G) components. Examples of other components include (A) a resin component other than a copolymer comprising a polyimide and a polyimide precursor; an organic compound containing a metal element, a sensitizer, a thermal polymerization inhibitor, an azole compound, and a hindered phenol compound.

[0229] The photosensitive resin composition may additionally contain a resin component other than (A) a copolymer comprising polyimide and a polyimide precursor. Examples of resin components that may be included in the photosensitive resin composition include polyimide, polyoxazole, polyoxazole precursor, phenolic resin, polyamide, epoxy resin, siloxane resin, acrylic resin, etc. The amount of these resin components is preferably in the range of 0.01 to 20 parts by mass per 100 parts by mass of (A) a copolymer comprising polyimide and a polyimide precursor.

[0230] The photosensitive resin composition may contain an organic compound containing a metal element. The organic compound containing a metal element preferably contains at least one metal element selected from the group consisting of titanium and zirconium in one molecule. As for the organic group, it is preferable to include a hydrocarbon group or a hydrocarbon group containing a heteroatom. By including the organic compound, the imidation rate of the polyimide precursor included in the photosensitive resin composition is increased, and the dielectric loss tangent of the cured film is reduced. Examples of usable organic titanium or zirconium compounds include those in which an organic group is bonded to a titanium atom or a zirconium atom via a covalent or ionic bond.

[0231] Specific examples of organic titanium or zirconium compounds are shown in I) to VII) below:

[0232] I) As for the chelate compound, a compound having two or more alkoxy groups is more preferable in that storage stability and good patterning of the photosensitive resin composition are obtained. Specific examples of chelate compounds include titanium bis(triethanolamine)diisopropoxide, titanium di(n-butoxide)bis(2,4-pentanedianate), titanium diisopropoxide bis(2,4-pentanedianate), titanium diisopropoxide bis(tetramethylheptanedianate), titanium diisopropoxide bis(ethylacetoacetate), and compounds in which the titanium atoms of these compounds are substituted with zirconium atoms, but are not limited to these.

[0233] II) Examples of tetraalkoxy compounds include titanium tetra(n-butoxide), titanium tetraethoxide, titanium tetra(2-ethylhexoxide), titanium tetraisobutoxide, titanium tetraisopropoxide, titanium tetramethoxide, titanium tetramethoxypropoxide, titanium tetramethylphenoxide, titanium tetra(n-nonyloxide), titanium tetra(n-propoxide), titanium tetrastearyloxide, titanium tetrakis[bis{2,2-(allyloxymethyl)butoxide}], and compounds in which the titanium atoms of these compounds are substituted with zirconium atoms, but are not limited to these.

[0234] III) Titanocene or zirconocene compounds include, for example, pentamethylcyclopentadienyltitanium trimethoxide, bis(η 5 -2,4-cyclopentadiene-1-yl)bis(2,6-difluorophenyl)titanium, bis(η 5 Examples include -2,4-cyclopentadiene-1-yl)bis(2,6-difluoro-3-(1H-pyrrole-1-yl)phenyl)titanium and compounds in which the titanium atoms of these compounds are substituted with zirconium atoms, but are not limited to these.

[0235] IV) Examples of monoalkoxy compounds include titanium tris(dioctyl phosphate)isopropoxide, titanium tris(dodecylbenzenesulfonate)isopropoxide, and compounds in which the titanium atoms of these compounds are substituted with zirconium atoms, but are not limited to these.

[0236] V) Examples of titanium oxide or zirconium oxide compounds include titanium oxide bis(pentanedianate), titanium oxide bis(tetramethylheptanedianate), phthalocyanine titanium oxide, and compounds in which the titanium atoms of these compounds are substituted with zirconium atoms, but are not limited to these.

[0237] VI) Examples of titanium tetraacetylacetonate or zirconium tetraacetylacetonate compounds include, for instance, titanium tetraacetylacetonate and compounds in which the titanium atoms of these compounds are substituted with zirconium atoms, but are not limited to these.

[0238] VII) Examples of titanate coupling agents include, but are not limited to, isopropyltridodecylbenzenesulfonyl titanate.

[0239] Among the above I) to VII), it is preferable that the organic titanium compound is at least one compound selected from the group consisting of I) titanium chelate compounds, II) tetraalkoxytitanine compounds, and III) titanocene compounds, in order to exhibit better dielectric loss tangent. In particular, titanium diisopropoxide bis(ethylacetoacetate), titanium tetra(n-butoxide), and bis(η 5 -2,4-cyclopentadiene-1-yl)bis(2,6-difluoro-3-(1H-pyrrole-1-yl)phenyl)titanium is preferred.

[0240] When incorporating an organic titanium or zirconium compound, the amount of incorporation is preferably 0.01 to 5 parts by mass and 0.1 to 3 parts by mass with respect to (A) a copolymer comprising a polyimide and a polyimide precursor. It is preferable that the amount of incorporation be 0.01 parts by mass or more, as this results in a good imidization rate of the resin composition and a dielectric loss tangent of the cured film, while it is preferable that the amount be 5 parts by mass or less, as this results in excellent storage stability.

[0241] A photosensitive resin composition can improve the imidation rate of a polyimide precursor contained in the resin composition and lower the dielectric loss tangent of a cured film using the resin composition by containing an organic compound containing the metal element. Although not bound by theory, it is thought that the reason for improving the imidation rate of a polyimide precursor is that the metal element contained in the organic compound containing the metal element coordinates to a carbonyl group derived from the ester group, amide group, and / or carboxyl group of the polyimide precursor, thereby lowering the electron density of the carbon atom of the carbonyl group and promoting the ring-closing reaction.

[0242] The photosensitive resin composition may optionally include a sensitizer to improve light sensitivity. Sensitizers include, for example, mihler ketone, 4,4'-bis(diethylamino)benzophenone, 2,5-bis(4'-diethylaminobenzal)cyclopentane, 2,6-bis(4'-diethylaminobenzal)cyclohexanone, 2,6-bis(4'-diethylaminobenzal)-4-methylcyclohexanone, 4,4'-bis(dimethylamino)chalcone, 4,4'-bis(diethylamino)chalcone, p-dimethylaminocinnamylideneindanone, p-dimethylaminobenzylideneindanone, 2-(p-dimethylaminophenylbiphenylene)-benzothiazole, 2-(p-dimethylaminophenylvinylene)benzothiazole, 2-(p-dimethylaminophenylvinylene)isonafththiazole, 1,3-bis(4'-dimethylaminobenzal)acetone, 1,3-Bis(4'-Diethylaminobenzal)acetone, 3,3'-Carbonyl-Bis(7-Diethylaminocoumarin), 3-Acetyl-7-Dimethylaminocoumarin, 3-Ethoxycarbonyl-7-Dimethylaminocoumarin, 3-Benzyloxycarbonyl-7-Dimethylaminocoumarin, 3-Methoxycarbonyl-7-Diethylaminocoumarin, 3-Ethoxycarbonyl-7-Diethylaminocoumarin, N-Phenyl-N'-Ethylethanolamine, N-Phenyldiethanolamine, Np-Tolyldiethanolamine, N-Phenylethanolamine, 4-Morpolinobenzophenone, Isoamyl dimethylaminobenzoate, Isoamyl diethylaminobenzoate, 2-Mercaptobenzimidazole, 1-Phenyl-5-Mercaptotetrazole, 2-Mercaptobenzothiazole, Examples include 2-(p-dimethylaminostyryl)benzoxazole, 2-(p-dimethylaminostyryl)benzthiazole, 2-(p-dimethylaminostyryl)naphtho(1,2-d)thiazole, 2-(p-dimethylaminobenzoyl)styrene, etc. These can be used individually or in combination of multiple types (e.g., 2 to 5 types). The amount of sensitizer is preferably 0.1 to 25 parts by mass per 100 parts by mass of (A) a copolymer containing a polyimide and a polyimide precursor.

[0243] The photosensitive resin composition may optionally include a thermal polymerization inhibitor to improve the stability of the viscosity and light sensitivity of the photosensitive resin composition when stored in a solution state, particularly one containing a solvent. Examples of thermal polymerization inhibitors used include hydroquinone, N-nitrosodiphenylamine, p-tert-butylcatechol, phenothiazine, N-phenylnaphthylamine, ethylenediaminetetraacetic acid, 1,2-cyclohexanediaminetetraacetic acid, glycol etherdiaminetetraacetic acid, 2,6-di-tert-butyl-p-methylphenol, 5-nitroso-8-hydroxyquinoline, 1-nitroso-2-naphthol, 2-nitroso-1-naphthol, 2-nitroso-5-(N-ethyl-N-sulfopropylamino)phenol, N-nitroso-N-phenylhydroxylamineammonium salt, N-nitroso-N(1-naphthyl)hydroxylamineammonium salt, etc. In addition, these thermal polymerization inhibitors may be used as a single type or as a mixture of two or more types. As for the amount of thermal polymerization inhibitor, the range is preferably 0.005 to 12 parts by mass per 100 parts by mass of (A) a copolymer containing polyimide and a polyimide precursor.

[0244] The photosensitive resin composition may optionally include an azole compound to suppress substrate discoloration when using a substrate made of copper or a copper alloy. Azole compounds include, for example, 1H-triazole, 5-methyl-1H-triazole, 5-ethyl-1H-triazole, 4,5-dimethyl-1H-triazole, 5-phenyl-1H-triazole, 4-t-butyl-5-phenyl-1H-triazole, 5-hydroxyphenyl-1H-triazole, phenyltriazole, p-ethoxyphenyltriazole, 5-phenyl-1-(2-dimethylaminoethyl)triazole, 5-benzyl-1H-triazole, hydroxyphenyltriazole, 1,5-dimethyltriazole, 4,5-diethyl-1H-triazole, 1H-benzotriazole, 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-[2-hydroxy-3,5-bis(α,α-dimethylbenzyl)phenyl]-benzotriazole, 2-(3,5-di-t-butyl-2-hydroxyphenyl)benzotriazole, 2-(3-t-butyl-5-methyl-2-hydroxyphenyl)-benzotriazole, 2-(3,5-di-t-amyl-2-hydroxyphenyl)benzotriazole, 2-(2'-hydroxy-5'-t-octylphenyl)benzotriazole, hydroxyphenylbenzotriazole, tolyltriazole, 5-methyl-1H-benzotriazole, 4-methyl-1H-benzotriazole, 4-carboxy-1H-benzotriazole, 5-carboxy-1H-benzotriazole, 1H-tetrazole, 5-methyl-1H-tetrazole, Examples include 5-phenyl-1H-tetrazole, 5-amino-1H-tetrazole, 1-methyl-1H-tetrazole, etc. Particularly preferably, tolyltriazole, 5-methyl-1H-benzotriazole, and 4-methyl-1H-benzotriazole. In addition, these azole compounds may be used as a single type or as a mixture of two or more types.

[0245] The amount of the azole compound is preferably 0.1 to 20 parts by mass per 100 parts by mass of a copolymer containing (A) a polyimide and a polyimide precursor, and more preferably 0.5 to 5 parts by mass from the perspective of light sensitivity characteristics. If the amount of the azole compound is 0.1 parts by mass or more per 100 parts by mass of a copolymer containing (A) a polyimide and a polyimide precursor, discoloration of the surface of the copper or copper alloy is suppressed when the photosensitive resin composition is formed on copper or a copper alloy, while if it is 20 parts by mass or less, it is preferred because the light sensitivity is excellent.

[0246] The photosensitive resin composition may include a hindered phenol compound to suppress substrate discoloration when using a substrate made of copper or a copper alloy. Hindered phenol compounds include, for example, 2,6-di-t-butyl-4-methylphenol, 2,5-di-t-butyl-hydroquinone, octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, isooctyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 4,4'-methylenebis(2,6-di-t-butylphenol), 4,4'-thio-bis(3-methyl-6-t-butylphenol), 4,4'-butylidene-bis(3-methyl-6-t-butylphenol), and triethyleneglycol-bis[3-(3-t-butyl-5-methyl-4-hydroxyphenyl)propionate]. 1,6-hexanediol-bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], 2,2-thio-diethylenebis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], N,N' hexamethylenebis(3,5-di-t-butyl-4-hydroxy-hydrocinnamamide), 2,2'-methylene-bis(4-methyl-6-t-butylphenol), 2,2'-methylene-bis(4-ethyl-6-t-butylphenol), pentaerythrityl-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], tris-(3,5-di-t-butyl-4-hydroxybenzyl)-isocyanurate, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, 1,3,5-tris(3-hydroxy-2,6-dimethyl-4-isopropylbenzyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, 1,3,5-tris(4-t-butyl-3-hydroxy-2,6-dimethylbenzyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, 1,3,5-tris(4-s-butyl-3-hydroxy-2,6-dimethylbenzyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, 1,3,5-Tris[4-(1-ethylpropyl)-3-hydroxy-2,6-dimethylbenzyl]-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, 1,3,5-Tris[4-triethylmethyl-3-hydroxy-2,6-dimethylbenzyl]-1,3,5-Triazine-2,4,6-(1H,3H,5H)-trione, 1,3,5-Tris(3-hydroxy-2,6-dimethyl-4-phenylbenzyl)-1,3,5-Triazine-2,4,6-(1H,3H,5H)-trione, 1,3,5-Tris(4-t-butyl-3-hydroxy-2,5,6-trimethylbenzyl)-1,3,5-Triazine-2,4,6-(1H,3H,5H)-trione, 1,3,5-Tris(4-t-butyl-5-ethyl-3-hydroxy-2,6-dimethylbenzyl)-1,3,5-Triazine-2,4,6-(1H,3H,5H)-trione, 1,3,5-Tris(4-t-butyl-6-ethyl-3-hydroxy-2-methylbenzyl)-1,3,5-Triazine-2,4,6-(1H,3H,5H)-trione, 1,3,5-Tris(4-t-butyl-6-ethyl-3-hydroxy-2,5-dimethylbenzyl)-1,3,5-Triazine-2,4,6-(1H,3H,5H)-trione, 1,3,5-Tris(4-t-butyl-5,6-diethyl-3-hydroxy-2-methylbenzyl)-1,3,5-Triazine-2,4,6-(1H,3H,5H)-trione, Examples include 1,3,5-tris(4-t-butyl-3-hydroxy-2-methylbenzyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, 1,3,5-tris(4-t-butyl-3-hydroxy-2,5-dimethylbenzyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, 1,3,5-tris(4-t-butyl-5-ethyl-3-hydroxy-2-methylbenzyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, but are not limited to these. Among these, 1,3,5-tris(4-t-butyl-3-hydroxy-2,6-dimethylbenzyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione is particularly preferred.

[0247] The amount of hindered phenol compound is preferably 0.1 to 20 parts by mass per 100 parts by mass of a copolymer containing (A) a polyimide and a polyimide precursor, and more preferably 0.5 to 10 parts by mass from the perspective of light sensitivity characteristics. If the amount of hindered phenol compound is 0.1 parts by mass or more per 100 parts by mass of a copolymer containing (A) a polyimide and a polyimide precursor, discoloration and corrosion of the copper or copper alloy are prevented, for example, when a photosensitive resin composition is formed on copper or a copper alloy, it is preferable that the light sensitivity is excellent if it is 20 parts by mass or less.

[0248] <Polyimide Cured Film and Method for Manufacturing the Same>

[0249] The present disclosure also provides a method for manufacturing a polyimide cured film, comprising a process of converting a photosensitive resin composition into polyimide. The method for manufacturing a polyimide cured film of the present disclosure is, for example, the following processes (1) to (5):

[0250] (1) A process of applying a photosensitive resin composition of the present disclosure onto a substrate to form a photosensitive resin layer on the substrate;

[0251] (2) A process of heating and drying the obtained photosensitive resin layer;

[0252] (3) Process of exposing the photosensitive resin layer after heating and drying;

[0253] (4) A process for developing a photosensitive resin layer after exposure; and

[0254] (5) A process of heat-treating the photosensitive resin layer after development to form a polyimide cured film; includes.

[0255] In a method for manufacturing a cured film, the photosensitive resin composition used preferably comprises 100 parts by mass of a copolymer comprising a polyimide and a polyimide precursor, 0.5 to 30 parts by mass of a photosensitive agent, and 100 to 1000 parts by mass of a solvent. It is more preferable to include a photoradical polymerization initiator as the photosensitive agent, and it is even more preferable that the photosensitive resin composition is of the negative type.

[0256] The specific process for the method of manufacturing a cured film can be carried out according to the processes (1) to (5) of the method of manufacturing a cured film described above. Below, typical embodiments of each process will be described.

[0257] (1) Photosensitive resin layer formation process

[0258] In this process, the photosensitive resin composition of the present disclosure is applied onto a substrate, and if necessary, subsequently dried to form a photosensitive resin layer. As for the application method, methods conventionally used for applying photosensitive resin compositions, such as applying with a spin coater, bar coater, blade coater, curtain coater, screen printer, etc., or applying by spraying with a spray coater, may be used.

[0259] (2) Heating and drying process

[0260] If necessary, the photosensitive resin composition film can be heated and dried. As a drying method, methods such as air drying, heat drying using an oven or hot plate, or vacuum drying are used. In addition, it is preferable to dry the film under conditions where imidization of the polyimide precursor portion (polyamic acid ester) of the copolymer (A) in the photosensitive resin composition does not occur. Specifically, when air drying or heat drying is performed, drying can be carried out at 20°C to 140°C for 1 minute to 1 hour. By the above, a photosensitive resin layer can be formed on a substrate.

[0261] (3) Photolithography process

[0262] In this process, the photosensitive resin layer formed above is exposed. As an exposure device, for example, an exposure device such as a contact aligner, a mirror projection, or a stepper is used. Exposure can be performed either through a photomask or reticle having a pattern or directly. The light source used for exposure is, for example, an ultraviolet light source.

[0263] After exposure, for purposes such as improving light sensitivity, post-exposure baking (PEB) and / or pre-development baking may be performed using any combination of temperature and time as needed. The range of baking conditions is preferably a temperature of 40 to 120°C and a time of 10 seconds to 240 seconds, but is not limited to this range as long as it does not impair the characteristics of the negative-type photosensitive resin composition of the present embodiment.

[0264] (4) Development process

[0265] In this process, a photosensitive resin layer is developed after exposure to form a relief pattern. If the photosensitive resin composition is of the negative type, unexposed portions of the photosensitive resin layer are developed and removed. As a developing method for developing the photosensitive resin layer after exposure (irradiation), any method can be selected from conventionally known photoresist developing methods, such as the rotary spray method, the puddle method, or the immersion method involving ultrasonic treatment. Additionally, if necessary, a post-development bake may be performed at any combination of temperature and time for the purpose of preparing the shape of the relief pattern after development. As for the developer used for development, for example, a solvent for the negative-type photosensitive resin composition, or a combination of the solvent and a non-solvent, is preferred. Preferably as the primary solvent, for example, N-methyl-2-pyrrolidone, N-cyclohexyl-2-pyrrolidone, N,N-dimethylacetamide, cyclopentanone, cyclohexanone, γ-butyrolactone, α-acetyl-γ-butyrolactone, etc. Preferably as the secondary solvent, for example, toluene, xylene, methanol, ethanol, isopropyl alcohol, ethyl lactate, propylene glycol methyl ether acetate, and water, etc. When using a mixture of the primary solvent and the secondary solvent, it is preferable to adjust the ratio of the secondary solvent to the primary solvent based on the solubility of the polymer in the negative-type photosensitive resin composition. In addition, two or more types of each solvent, for example, several types, may be combined and used. In the process of developing a photosensitive resin layer after exposure, it is preferable to perform the coating to developing process so that a photosensitive resin layer with a film thickness of 10 μm to 15 μm is obtained.

[0266] (5) Polyimide cured film formation process

[0267] In this process, the relief pattern obtained by the above phenomenon is heated to dilute the photosensitive component, and at the same time, (A) copolymer is imidized to convert it into a cured relief pattern made of polyimide. Various methods can be selected for heat curing, such as using a hot plate, using an oven, or using a heating oven capable of setting a temperature program. Heating can be performed, for example, at 160°C to 400°C for 30 minutes to 5 hours. Air may be used as the atmosphere gas during heat curing, or an inert gas such as nitrogen or argon may be used. In this way, a cured relief pattern (polyimide cured film) can be manufactured.

[0268] The method for manufacturing a polyimide cured film of the present disclosure is, for example, a method for manufacturing a cured film comprising applying a photosensitive resin composition of the present disclosure onto a substrate, performing an exposure treatment, a development treatment, and subsequently a heat treatment, wherein the cured film preferably has a dielectric loss tangent of 0.003 to 0.011 when measured at 40 GHz using a perturbation-type split cylinder resonance technique. Additionally, the dielectric loss tangent can be measured by the perturbation-type split cylinder resonance technique shown in the examples described below.

[0269] The present disclosure also provides a polyimide cured film obtained from the photosensitive resin composition described above. In terms of transmission loss derived from the dielectric, the cured film preferably has a dielectric loss tangent at a frequency of 40 GHz using a perturbation-type split-cylinder resonator technique of 0.003 to 0.011, and the lower the lower, the more desirable it is. In addition, in terms of multilayering of the redistribution layer, it is desirable for the cured film to have low curing shrinkage, and it is desirable for the residual film rate after curing to be 81% to 93%. By having a rate of 81% or higher, the deformation of the redistribution layer derived from copper wiring during redistribution becomes minor. As a redistribution material for copper wiring used for high-speed transmission, the residual film rate after curing (RFA) and the dielectric loss tangent (tanδ)40 ) quotient (RFA / tanδ 40 It is desirable for this to be within a certain range, and the value of the dielectric loss tangent at 40 GHz is 0.003 < tanδ 40 Satisfies < 0.011, and also satisfies the residual film rate after curing as a ratio of 0.81 < RFA < 0.93 (as a percentage of 81% < RFA < 93%), and

[0270] The following formula:

[0271] 85 < RFA (ratio) / tanδ 40 < 175

[0272] It is desirable to satisfy RFA (ratio) / tanδ 40 By being in the range greater than 85 and less than 175, a polyimide cured material desirable as a redistribution material for copper wiring used in high-speed transmission is obtained. RFA (ratio) / tanδ 40 It is, more preferably, greater than 100 and less than 170.

[0273] <Semiconductor Device>

[0274] The present disclosure may also provide a semiconductor device having a cured relief pattern obtained by the method for manufacturing a cured relief pattern described above, using the photosensitive resin composition of the present disclosure. Accordingly, a semiconductor device having a substrate which is a semiconductor element and a cured relief pattern of polyimide formed on the substrate by the method for manufacturing a cured relief pattern described above is provided. Furthermore, the present disclosure may also be applied to a method for manufacturing a semiconductor device using a semiconductor element as a substrate and including the method for manufacturing a cured relief pattern described above as part of the process. The semiconductor device may be manufactured by forming the cured relief pattern formed by the method for manufacturing a cured relief pattern as a surface protective film, an interlayer insulating film, an insulating film for redistribution, a protective film for a flip-chip device, or a protective film for a semiconductor device having a bump structure, and by combining it with a known method for manufacturing a semiconductor device.

[0275] The polyimide included in the cured relief pattern (polyimide cured film) formed from a photosensitive resin composition is of the following general formula (10):

[0276] [Chemical Formula 21]

[0277]

[0278] It is preferable to have a structure represented by {in general formula (10), X1, X2, X3, Y1, and Y2 are identical to X1, X2, X3, Y1, and Y2 in general formula (1), n1 is an integer from 2 to 30, and n2 and n3 are integers from 2 to 150.}

[0279] <Display device>

[0280] The present disclosure may also provide a display device comprising a display element and a cured film formed on the upper surface of the display element using the photosensitive resin composition of the present disclosure, wherein the cured film is the cured relief pattern described above. Here, the cured relief pattern may be laminated in direct contact with the display element or laminated with another layer in between. Examples of the cured film include a surface protection film, an insulating film, and a planarization film for a TFT liquid crystal display element and a color filter element, a protrusion for an MVA type liquid crystal display device, and a barrier for an organic EL element cathode.

[0281] In addition to applications for semiconductor devices as described above, the photosensitive resin composition of the present disclosure is also useful for interlayer insulation of multilayer circuits, cover coatings for flexible copper coating plates, solder resist films, liquid crystal alignment films, etc.

[0282] <Method for manufacturing a photosensitive resin composition>

[0283] The method for preparing a photosensitive resin composition of the present disclosure comprises: (A) a step of preparing a copolymer resin by the method of the present disclosure as described in "(A) a method for preparing a copolymer resin comprising a polyimide and a polyimide precursor"; and (B) a step of mixing 100 parts by mass of (A) the copolymer resin, 0.5 to 30 parts by mass of a photopolymerization initiator, and (C) 100 to 1000 parts by mass of a solvent to obtain a photosensitive resin composition. Optionally, the (D) silane coupling agent, (E) radical polymerizable compound, (F) thermal crosslinking agent, (G) filler, and (H) other components described above may be mixed.

[0284] Examples

[0285] The physical properties of the photosensitive resin compositions in the examples, comparative examples, and manufacturing examples of the present disclosure were measured and evaluated according to the following methods.

[0286] <Measurement and Evaluation Methods>

[0287] (1) Weight-average molecular weight

[0288] The weight average molecular weight (Mw) of the diamine oligomer and copolymer resin was measured by gel permeation chromatography (standard polystyrene equivalent). The column used for measurement was the Shodex 805M / 806M series manufactured by Showa Denko, the standard monodisperse polystyrene was selected as Shodex STANDARD SM-105 manufactured by Showa Denko, the developing solvent was N-methyl-2-pyrrolidone, and the detector was the Shodex RI-930 manufactured by Showa Denko.

[0289] (2) Measurement of the introduction rate of imide structure in copolymer resin

[0290] 10 g of copolymer resin was dissolved in a mixed solvent (weight ratio 90:10) consisting of γ-butyrolactone and DMSO, and a polymer solution was prepared by adjusting the amount of solvent so that the viscosity was approximately 25 poise. The polymer solution was rotary-coated onto a 6-inch silicon wafer (manufactured by Fujimi Electronics Co., Ltd., thickness 625 ± 25 μm) using a coater developer (D-Spin60A type, manufactured by SOKUDO), and heated and dried on a hot plate at 110°C for 3 minutes to form a photosensitive resin layer approximately 10 μm thick. The photosensitive resin layer was measured using an ATR-FTIR measuring device (Nicolet Continuum, manufactured by Thermo Fisher Scientific) with a Si prism at a measurement range of 4000 cm⁻¹. -1 ~ 700 cm -1 , measurements were performed 50 times. 1380 cm of the hardened film -1 Near (1350 cm) -1 ~ 1450 cm -1 , in the case of multiple peaks, the peak height of the peak with the maximum intensity and 1500 cm -1 Near (1460 cm) -1 ~ 1550 cm -1 In the case of multiple peaks, the value divided by the peak height of the peak with the maximum peak intensity was set as the imidation index 1. The value divided by the imidation index 2 of a cured film separately cured at 350°C under the same conditions was calculated as the imide structure introduction rate.

[0291] (3) Resolution and development time of the cured relief pattern on the Cu substrate

[0292] On a 6-inch silicon wafer (manufactured by Fujimi Electronics Co., Ltd., thickness 625 ± 25 μm), a sputtering device (L-440S-FHL type, manufactured by Canon Arnelva) was used to sputter Ti with a thickness of 200 nm and Cu with a thickness of 400 nm in that order. Subsequently, a photosensitive resin composition prepared by the method described below was applied onto the wafer using a coater developer (D-Spin60A type, manufactured by SOKUDO), and a photosensitive resin layer with a thickness of approximately 13.5 μm was formed by heating and drying on a hot plate at 110°C for 3 minutes. On this photosensitive resin layer, an energy of 600 mJ / cm² was irradiated by a Prisma GHI (manufactured by Ultratech Co.) equipped with an i-line filter using a mask having a test pattern formed thereon. Next, the photosensitive resin layer was spray-developed using a coater developer (D-Spin60A type, manufactured by SOKUDO) with cyclopentanone as the developer, and rinsed with propylene glycol methyl ether acetate to obtain a relief pattern on Cu. The time of the spray development at this time was defined as the development time. The wafer having the relief pattern formed on Cu was heat-treated at 230°C for 2 hours under a nitrogen atmosphere using a temperature-programming curer (VF-2000 type, manufactured by Koyo Lindberg) to obtain a cured relief pattern on Cu consisting of resin with a thickness of about 10 μm. The manufactured relief pattern was observed under an optical microscope to determine the size of the minimum aperture pattern. At this time, if the area of ​​the opening of the obtained pattern is 1 / 2 or more of the corresponding pattern mask opening area, it is considered to be resolved, and the resolution is determined based on the following evaluation criteria based on the length of the mask opening edge (size of the opening pattern) corresponding to the one having the minimum area among the resolved openings.

[0293] (metewand)

[0294] A: The size of the minimum aperture pattern is less than 10 µm

[0295] B: The size of the minimum aperture pattern is 10 µm or more and less than 15 µm

[0296] C: Minimum aperture pattern size is 15 µm or more and less than 20 µm

[0297] D: Minimum aperture pattern size is 20 µm or larger

[0298] In the present disclosure, results greater than C are considered desirable.

[0299] (4) Measurement of genetic properties (relative permittivity: Dk, dielectric loss tangent: Df)

[0300] A sputtered Al wafer substrate was prepared by sputtering 100 nm-thick aluminum (Al) onto a 6-inch silicon wafer (manufactured by Fujimi Electronics Co., Ltd., thickness 625 ± 25 μm) using a sputtering apparatus (Model L-440S-FHL, manufactured by Canon Anelva Corporation). The photosensitive resin composition prepared by the method described later was spin-coated onto the sputtered Al wafer substrate using a spin coater (Model D-spin60A, manufactured by SOKUDO Co., Ltd.), and heated and dried at 110 °C for 180 seconds to form a photosensitive resin layer with a thickness of about 13.5 μm. Thereafter, the entire surface was exposed to ghi rays at an exposure dose of 600 mJ / cm² using an aligner (PLA-501F, manufactured by Canon Inc.), and a heat curing treatment was performed at 230 °C for 2 hours under a nitrogen atmosphere using a vertical cure oven (manufactured by Koyo Lindberg, model name VF-2000B), to produce a cured film made of a resin with a thickness of about 10 μm on the Al wafer. This cured film was cut using a dicing saw (manufactured by Disco, model name DAD-2H / 6T) into pieces of 80 mm in length and 62 mm in width (for 10 GHz measurement) and 40 mm in length and 30 mm in width (for 40 GHz measurement), immersed in a 10% hydrochloric acid aqueous solution to be peeled off from the silicon wafer, to obtain film samples. The relative dielectric constant (Dk) and dielectric loss tangent (Df) of the film samples at 10 GHz and 40 GHz were respectively measured by the resonator perturbation method. The details of the measurement method are as follows.

[0301] (Measurement Method)

[0302] Perturbation-type split cylinder resonator method

[0303] (Humidity Conditioning of Measurement Samples)

[0304] Standing still at 23 °C / 50% RH for 24 hours

[0305] (Measurement Conditions)

[0306] 23 °C / 50% RH

[0307] (Device configuration)

[0308] Network Analyzer :

[0309] PNA Network analyzer N5224B

[0310] (Manufactured by KEYSIGHT)

[0311] Split Cylinder Resonator :

[0312] CR-710 (Manufactured by Kanto Electronics Application Development Co., Ltd., Measurement frequency: approx. 10 GHz)

[0313] CR-740 (Manufactured by Kanto Electronics Application Development Co., Ltd., Measurement frequency: approx. 40 GHz)

[0314] (5) Measurement of residual film after curing

[0315] On a 6-inch silicon wafer (manufactured by Fujimi Electronics Co., Ltd., thickness 625 ± 25 μm), a sputtering device (L-440S-FHL type, manufactured by Canon Annelvade) was used to sputter Ti with a thickness of 200 nm and Cu with a thickness of 400 nm in that order. Subsequently, a photosensitive resin composition prepared by the method described below was applied onto the wafer using a coater developer (D-Spin60A type, manufactured by SOKUDO), and a photosensitive resin layer with a thickness of about 13.5 μm was formed by heating and drying on a hot plate at 110°C for 3 minutes. After that, full-surface exposure was performed using an aligner (PLA-501F, manufactured by Canon) with a ghi line having an exposure amount of 800 mJ / cm². Afterwards, the film formed on the wafer was spray-developed using a developer (D-SPIN 636 type, manufactured by Dai Nippon Screen Manufacturer, Japan) with cyclopentanone. Then, it was rinsed with propylene glycol methyl ether acetate and dried using a spin dryer. The film thickness after this development was measured and set as film thickness 1. The film after this development was further heat-cured using a bell-shaped curer (manufactured by Koyo Lindberg, model name VF-2000B) at 230°C for 2 hours under a nitrogen atmosphere. The film thickness after this heat treatment was measured and set as film thickness 2. Using these film thicknesses, the residual film ratio (ratio and %) after curing was calculated from the following formula.

[0316] Residual film ratio after curing (ratio) = Film thickness 2 / Film thickness 1

[0317] Residual film percentage after curing (%) = Film thickness 2 / Film thickness 1 × 100

[0318] Also, the residual film rate (ratio) after curing and the dielectric loss tangent (tanδ 40 ) quotient (RFA (ratio) / tanδ 40 ) produced.

[0319] (6) Copper adhesion evaluation

[0320] On a 6-inch silicon wafer (manufactured by Fujimi Electronics Co., Ltd., thickness 625 ± 25 μm), a sputtering device (L-440S-FHL type, manufactured by Canon Arnelva) was used to sputter Ti with a thickness of 200 nm and Cu with a thickness of 400 nm in that order. Subsequently, a photosensitive resin composition prepared by the method described below was applied onto the wafer using a coater developer (D-Spin60A type, manufactured by SOKUDO), and a photosensitive resin layer with a thickness of about 13.5 μm was formed by heating and drying on a hot plate at 110°C for 3 minutes. Afterwards, the entire surface was exposed using an aligner (PLA-501F, manufactured by Canon) with a ghi line of an exposure amount of 800 mJ / ㎠, and a heat curing treatment was performed at 230°C for 2 hours under a nitrogen atmosphere using a vertical curer (manufactured by Koyo Lindbergh, model name VF-2000B) to produce a cured film made of resin with a thickness of about 10 μm on a Cu wafer. After the heat treatment, the adhesion characteristics between the copper substrate and the cured resin film were evaluated based on the following criteria in accordance with the cross-cut method of JIS K 5600-5-6.

[0321] (metewand)

[0322] A: The grid number of the cured resin film adhered to the substrate is 80 or more to 100

[0323] B: The grid number of the cured resin film adhered to the substrate is 60 or more to less than 80

[0324] C: The grid number of the cured resin film adhered to the substrate is 40 or more ~ ​​less than 60

[0325] D: The grid number of the cured resin film adhered to the substrate is less than 40

[0326] In the present disclosure, results B or higher are considered desirable.

[0327] (7) Conservation stability

[0328] The photosensitive resin composition described below was prepared and left to stand at room temperature for 24 hours. Afterward, viscosity measurements were performed using an E-type viscometer (Viscomate VM-150III manufactured by Toki Industry) under conditions of 23°C. This initial viscosity was set as viscosity 1. The photosensitive resin composition after measurement was stored at 40°C for 3 days, and viscosity measurements were performed again under the same conditions. The viscosity after this heat treatment was set as viscosity 2. Using these viscosities, storage stability was calculated from the following formula.

[0329] Rate of change in viscosity (%) = (|viscosity 2 - viscosity 1| / viscosity 1) × 100

[0330] (metewand)

[0331] A: Viscosity change rate less than 3%

[0332] B: Viscosity change rate is 3% or more and less than 5%

[0333] C: Viscosity change rate is 5% or more and less than 10%

[0334] D: Viscosity change rate of 10% or more

[0335] In the present disclosure, results greater than C are considered desirable.

[0336] <Manufacture of Diamine X-1>

[0337] A 5 L 4-neck flask was evaporated with Ar, and 172.02 g of 4,4'-butylindenebis(6-tert-butyl-m-cresol), 155.84 g of 4-chloronitrobenzene, and 1.5 L of DMF were added and stirred. 186.42 g of K2CO3 was added thereto, and the mixture was heated at 150 °C for 5 hours, after which the loss of raw materials and intermediates was confirmed by TLC. After cooling to room temperature, the reaction mixture was filtered, and the filtrate was concentrated under reduced pressure at 80 °C. The concentrated residue was diluted with 1.6 L of deion-exchanged water, and an additional 2.5 L of ethyl acetate was added for three rounds of fractional purification. The organic layer was recovered and dried by adding MgSO4. After drying, the mixture was filtered to remove impurities, dissolved in 800 mL of toluene, and added to 4.0 L of methanol, which was stirred for 30 minutes. After stirring, the filtrate was recovered and dried at 80 °C for 12 hours. The reaction product obtained by drying was placed into a 5 L 4-neck flask substituted with Ar, and an additional 19.04 g of 5% Pd / C (EA) and 1.9 L of THF were added and stirred. The flask was heated to 40 °C, and H2 bubbling (10 mL / min) was performed to carry out the reduction reaction for 24 hours. The reaction solution was filtered using Celite, the fraction of the target product was recovered by silica gel chromatography, and diamine X-1 was obtained by concentrating under reduced pressure.

[0338] <(A) Preparation of a diamine compound having repeating units of a polyimide structure>

[0339] Synthesis of Polyimide (Diamine Oligomer W-1):

[0340] 41.6 g of 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride (BPADA) as the acid component, 34.0 g of 2,2'-dimethylbiphenyl-4,4'-diamine (m-TB) as the diamine component, and 176.4 g of N-methylpyrrolidone (NMP) as the solvent were added to a 0.5-liter separable flask equipped with a Dean Stark tube and a condenser, and dissolved while stirring. Additionally, 42.3 g of toluene was added and stirred, after which the temperature was raised to 185 °C under a nitrogen stream. After stirring at 185 °C for 2.5 hours, the toluene in the system and the water produced by imidization were removed over a period of 1.5 hours. Subsequently, the mixture was cooled to room temperature to obtain a solution of diamine oligomer W-1 having repeating units of a polyimide structure. The weight-average molecular weight (Mw) of this diamine oligomer W-1 was measured to be 3,000. of diamine oligomer W-1 1 H-NMR measurements were performed, and the imide closure rate was confirmed by comparing the peaks derived from the amide bonds with the peaks derived from the aromatic rings of the polyimide. The imide closure rate was 99% or higher.

[0341] Synthesis of Polyimide (Diamine Oligomer W-2):

[0342] A solution of diamine oligomer W-2 was obtained by carrying out the reaction in the same manner as described in the synthesis method of diamine oligomer W-1, except that in the synthesis method of diamine oligomer W-1 above, 52.6 g of 2,2-bis[4-(4-aminophenoxy)-3-methylphenyl]propane (MBAPP), 220 g of NMP as a solvent, and 52.8 g of toluene were used instead of 34.0 g of m-TB. The weight-average molecular weight (Mw) of this diamine oligomer W-2 was measured to be 5,000. In the same manner as diamine oligomer W-1. 1 The imide closure rate obtained from H-NMR measurement was over 99%.

[0343] Synthesis of Polyimide (Diamine Oligomer W-3):

[0344] A solution of diamine oligomer W-3 was obtained by carrying out the reaction in the same manner as described in the synthesis method of diamine oligomer W-1, except that in the synthesis method of diamine oligomer W-1 above, 24.8 g of 4,4'-oxydiphthalic dianhydride (ODPA) was used instead of 41.6 g of BPADA, 65.7 g of 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP) was used instead of 34.0 g of m-TB, 211 g of NMP was used as a solvent, and 50.7 g of toluene was used. The weight-average molecular weight (Mw) of this diamine oligomer W-3 was measured to be 2,700. In the same manner as diamine oligomer W-1. 1 The imide closure rate obtained from H-NMR measurement was over 99%.

[0345] Synthesis of Polyimide (Diamine Oligomer W-4):

[0346] A solution of diamine oligomer W-4 was obtained by carrying out the reaction in the same manner as described in the synthesis method of diamine oligomer W-1, except that in the synthesis method of diamine oligomer W-1 above, 24.8 g of ODPA was used instead of 41.6 g of BPADA, 70.2 g of MBAPP was used instead of 34.0 g of m-TB, 222 g of NMP was used as a solvent, and 53.0 g of toluene was used. The weight-average molecular weight (Mw) of this diamine oligomer W-4 was measured to be 3,000. In the same manner as diamine oligomer W-1 1 The imide closure rate obtained from H-NMR measurement was over 99%.

[0347] Synthesis of Polyimide (Diamine Oligomer W-5):

[0348] A solution of diamine oligomer W-5 was obtained by carrying out the reaction in the same manner as described in the synthesis method of diamine oligomer W-1, except that in the synthesis method of diamine oligomer W-1 above, 24.8 g of ODPA was used instead of 41.6 g of BPADA, 90.4 g of diamine X-1 was used instead of 34.0 g of m-TB, 269 g of NMP was used as a solvent, and 64.5 g of toluene was used. The weight-average molecular weight (Mw) of this diamine oligomer W-5 was measured to be 3,500. In the same manner as diamine oligomer W-1. 1 The imide closure rate obtained from H-NMR measurement was over 99%.

[0349] Synthesis of Polyimide (Diamine Oligomer W-6):

[0350] A solution of diamine oligomer W-6 was obtained by carrying out the reaction in the same manner as described in the synthesis method of diamine oligomer W-1, except that 55.8 g of 9,9-bis(4-aminophenyl)fluorene (BAFL), 188 g of NMP as a solvent, and 45.1 g of toluene were used instead of 34.0 g of m-TB in the synthesis method of diamine oligomer W-1 above. The weight-average molecular weight (Mw) of this diamine oligomer W-6 was measured to be 2,900. In the same manner as diamine oligomer W-1 1 The imide closure rate obtained from H-NMR measurement was over 99%.

[0351] Synthesis of Polyimide (Diamine Oligomer W-7):

[0352] A solution of diamine oligomer W-7 was obtained by carrying out the reaction in the same manner as described in the synthesis method of diamine oligomer W-1, except that 37.2 g of BAFL, 145 g of NMP as a solvent, and 34.7 g of toluene were used instead of 34.0 g of m-TB in the synthesis method of diamine oligomer W-1 above. The weight-average molecular weight (Mw) of this diamine oligomer W-7 was measured to be 8,200. In the same manner as diamine oligomer W-1 1 The imide closure rate obtained from H-NMR measurement was over 99%.

[0353] Synthesis of Polyimide (Diamine Oligomer W-8):

[0354] A solution of diamine oligomer W-8 was obtained by carrying out the reaction in the same manner as described in the synthesis method of diamine oligomer W-1, except that in the synthesis method of diamine oligomer W-1 above, 24.8 g of ODPA was used instead of 41.6 g of BPADA, 51.2 g of 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl (TFMB) was used instead of 34.0 g of m-TB, 177 g of NMP was used as a solvent, and 42.6 g of toluene was used. The weight-average molecular weight (Mw) of this diamine oligomer W-8 was measured to be 2,500. In the same manner as diamine oligomer W-1. 1 The imide closure rate obtained from H-NMR measurement was over 99%.

[0355] Synthesis of Polyimide (Diamine Oligomer W-9):

[0356] A solution of diamine oligomer W-9 was obtained by carrying out the reaction in the same manner as described in the synthesis method of diamine oligomer W-1, except that in the synthesis method of diamine oligomer W-1 above, 35.5.8 g of 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA) was used instead of 41.6 g of BPADA, 65.7 g of 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP) was used instead of 34.0 g of m-TB, 236 g of NMP was used as a solvent, and 56.7 g of toluene was used. The weight-average molecular weight (Mw) of this diamine oligomer W-9 was measured to be 3,200. In the same manner as diamine oligomer W-1. 1 The imide closure rate obtained from H-NMR measurement was over 99%.

[0357] Synthesis of Polyimide (Diamine Oligomer W-10):

[0358] A solution of diamine oligomer W-10 was obtained by carrying out the reaction in the same manner as described in the synthesis method of diamine oligomer W-1, except that in the synthesis method of diamine oligomer W-1 above, 20.7 g of 1,10-diaminodecane was used instead of 34.0 g of m-TB, and 249 g of NMP and 34.9 g of toluene were used as solvents. The weight-average molecular weight (Mw) of this diamine oligomer W-10 was measured to be 3,700. In the same manner as diamine oligomer W-1. 1 The imide closure rate obtained from H-NMR measurement was over 99%.

[0359] <(A) Preparation of copolymer resin containing polyimide and polyimide precursor>

[0360] Synthesis of Polymer A-1:

[0361] As the acid component, 20.9 g of BPADA was placed in a 1-liter separable flask, and 10.9 g of 2-hydroxyethyl methacrylate (HEMA) and 42 g of γ-butyrolactone (GBL) were added. 6.4 g of pyridine was added while stirring at room temperature, and the mixture was heated at 50 °C for 4 hours. After the exothermic reaction was complete, the mixture was cooled to room temperature. It was then left to stand for an additional 16 hours to obtain the reaction mixture.

[0362] Next, under ice cooling, a solution of 16.3 g of dicyclohexylcarbodiimide (DCC) dissolved in 16.3 g of GBL was added to the reaction mixture over 40 minutes while stirring, followed by the addition of 91.0 g of GBL. Subsequently, as the diamine component, a solution of 101.7 g of the NMP solution of the diamine oligomer W-2 prepared above mixed with 66.5 g of GBL was added over 20 minutes while stirring. Additionally, a solution of 2.4 g of m-TB dissolved in 7 g of GBL was added over 5 minutes while stirring. After stirring at room temperature for 4 hours, 6.4 g of ethyl alcohol was added and stirred for 30 minutes, followed by the addition of 49.0 g of GBL. The precipitate formed in the reaction mixture was removed by filtration to obtain the reaction solution.

[0363] The obtained reaction solution was added to 1000 g of ethyl alcohol to produce a precipitate consisting of a crude polymer. The resulting crude polymer was filtered and collected, and dissolved in 270 g of γ-butyrolactone to obtain a crude polymer solution. The obtained crude polymer solution was applied to an anion exchange resin ("Amberlist" manufactured by Organo Co., Ltd. TMA polymer solution was obtained by purification using [15JWET]. The obtained polymer solution was added dropwise to 3800 g of water to precipitate the polymer, and the obtained precipitate was filtered and collected, then vacuum dried to obtain powdered polymer A-1. The weight-average molecular weight (Mw) of this polymer A-1 was 30,000, and the imide group introduction rate was 0.43. In addition, the imide group concentration U per repeating unit of the polyimide obtained from polymer A-1 was 16.0 wt%. Furthermore, the "imide group concentration U" was calculated by converting it to the polyimide of a polyimide cured film obtained by heating and curing at 350 ℃ (the same applies hereinafter).

[0364] Synthesis of Polymer A-2:

[0365] As the acid component, 15.2 g of BPADA was placed in a 1-liter separable flask, and 7.9 g of HEMA and 30.8 g of γ-butyrolactone (GBL) were added. 4.6 g of pyridine was added while stirring at room temperature, and the mixture was heated at 50 °C for 4 hours. After the exothermic reaction was complete, the mixture was cooled to room temperature. It was then left to stand for an additional 16 hours to obtain the reaction mixture.

[0366] Next, under ice cooling, a solution of 11.9 g of dicyclohexylcarbodiimide (DCC) dissolved in 11.9 g of GBL was added to the reaction mixture over 40 minutes while stirring, followed by the addition of 91.0 g of GBL. Subsequently, as the diamine component, a solution of 111.5 g of the NMP solution of the diamine oligomer W-1 prepared above mixed with 72.9 g of GBL was added over 20 minutes while stirring. After stirring for 4 hours at room temperature, 49.0 g of GBL was added. The precipitate formed in the reaction mixture was removed by filtration to obtain the reaction solution.

[0367] Polymer A-2 was obtained by carrying out the reaction in the same manner as described in the synthesis method of polymer A-1 for the subsequent purification process. The weight average molecular weight (Mw) of this polymer A-2 was 24,000, and the imide group introduction rate was 0.58. In addition, the imide group concentration U per repeating unit of the polyimide obtained from polymer A-2 was 20.1 wt%.

[0368] Synthesis of Polymer A-3:

[0369] As the acid component, 15.2 g of BPADA was placed in a 1-liter separable flask, and 7.9 g of HEMA (compound with the first substituent introduced) and 30.8 g of GBL were added. 4.6 g of pyridine was added while stirring at room temperature, and the mixture was heated at 50 °C for 4 hours. After the exothermic reaction was complete, the mixture was cooled to room temperature. It was then left to stand for an additional 16 hours to obtain the reaction mixture (Reaction 1).

[0370] In a separately prepared 0.5-liter 3-neck flask, 111.5 g of an NMP solution of diamine oligomer W-1 as the diamine component was mixed with 72.9 g of GBL, and while stirring under ice cooling, 3.1 g of 2-isocyanatoethyl methacrylate (a compound introducing a second substituent) was dissolved in 15.5 g of GBL, and stirring was carried out under ice cooling for 1 hour to obtain a reaction mixture solution with diamine oligomer W-1 (second reaction).

[0371] In parallel with the above second reaction, under ice cooling, a solution of 11.9 g of DCC dissolved in 20 g of GBL was added to the reaction mixture of the first reaction over a period of 40 minutes while stirring. Subsequently, as the diamine component, a reaction mixture solution containing the diamine oligomer W-1 obtained from the second reaction was added over a period of 60 minutes while stirring. After stirring for 4 hours at room temperature, 49.0 g of GBL was added. The precipitate formed in the reaction mixture was removed by filtration to obtain the reaction solution.

[0372] Polymer A-3 was obtained by carrying out the reaction in the same manner as described in the synthesis method of polymer A-1 for the subsequent purification process. The weight average molecular weight (Mw) of this polymer A-3 was 18,000, and the imide group introduction rate was 0.58. In addition, the imide group concentration U per repeating unit of the polyimide obtained from polymer A-3 was 20.1 wt%.

[0373] Synthesis of Polymer A-4:

[0374] Polymer A-4 was obtained by carrying out the reaction in the same manner as described in the synthesis method of Polymer A-1, except that in the synthesis method of Polymer A-1 above, 17.0 g of BPADA was used instead of 20.9 g of BPADA, 8.8 g of HEMA was used instead of 10.9 g of HEMA, 13.3 g of DCC was used instead of 16.3 g of DCC, and 127.2 g of NMP solution of Diamine Oligomer W-2 was used instead of 101.7 g of NMP solution of Diamine Oligomer W-2 and 2.4 g of m-TB. The weight-average molecular weight (Mw) of Polymer A-4 was 35,000, and the imide group introduction rate was 0.53. In addition, the imide group concentration U per repeating unit of the polyimide obtained from Polymer A-4 was 15.2 wt%.

[0375] Synthesis of Polymer A-5:

[0376] Polymer A-5 was obtained by carrying out the reaction in the same manner as described in the synthesis method of Polymer A-2, except that in the synthesis method of Polymer A-2, 8.1 g of ODPA was used instead of 15.2 g of BPADA, 7.1 g of HEMA was used instead of 7.9 g of HEMA, 10.7 g of DCC was used instead of 11.9 g of DCC, and 169.6 g of NMP solution of Diamine Oligomer W-3 was used instead of 111.5 g of NMP solution of Diamine Oligomer W-1. The weight average molecular weight (Mw) of Polymer A-5 was 22,000, and the imide group introduction rate was 0.63. In addition, the imide group concentration U per repeating unit of the polyimide obtained from Polymer A-5 was 20.5 wt%.

[0377] Synthesis of Polymer A-6:

[0378] Polymer A-6 was obtained by carrying out the reaction in the same manner as described in the synthesis method of Polymer A-2, except that in the synthesis method of Polymer A-2 above, 8.1 g of ODPA was used instead of 15.2 g of BPADA, 7.1 g of HEMA was used instead of 7.9 g of HEMA, 10.7 g of DCC was used instead of 11.9 g of DCC, and 176.7 g of NMP solution of Diamine Oligomer W-4 was used instead of 111.5 g of NMP solution of Diamine Oligomer W-1. The weight average molecular weight (Mw) of Polymer A-6 was 23,000, and the imide group introduction rate was 0.63. In addition, the imide group concentration U per repeating unit of the polyimide obtained from Polymer A-6 was 19.6 wt%.

[0379] Synthesis of Polymer A-7:

[0380] Polymer A-7 was obtained by carrying out the reaction in the same manner as described in the synthesis method of Polymer A-1, except that 12.4 g of ODPA was used instead of 20.9 g of BPADA, and 143.1 g of an NMP solution of diamine oligomer W-5 was used instead of 101.7 g of an NMP solution of diamine oligomer W-2 and 2.4 g of m-TB. The weight average molecular weight (Mw) of Polymer A-7 was 21,000, and the imide group introduction rate was 0.43. In addition, the imide group concentration U per repeating unit of the polyimide obtained from Polymer A-7 was 16.7 wt%.

[0381] Synthesis of Polymer A-8:

[0382] As the acid component, 12.4 g of ODPA was placed in a 1-liter separable flask, and 10.8 g of HEMA (the compound with the first substituent introduced) and 26.0 g of GBL were added. A reaction mixture was obtained by adding 6.3 g of pyridine while stirring at room temperature (Reaction 1). After the exothermic reaction ended, the mixture was cooled to room temperature and left to stand for an additional 16 hours.

[0383] Next, under ice cooling, a solution of 16.3 g of dicyclohexylcarbodiimide (DCC) dissolved in 16.3 g of GBL was added to the reaction mixture of the first reaction over 40 minutes while stirring. Subsequently, 1.1 g of allylamine (a compound with a second substituent introduced) was dissolved in 5.5 g of GBL, and the GBL solution was added over 5 minutes while stirring (second reaction). To the reaction mixture of the second reaction, a solution of 143.1 g of NMP solution of diamine oligomer W-5 dissolved in 93.6 g of GBL was added as a diamine component over 60 minutes while stirring. After stirring at room temperature for 4 hours, 6.4 g of ethyl alcohol was added and stirred for 30 minutes, and then 49.0 g of GBL was added. The precipitate formed in the reaction mixture was removed by filtration to obtain the reaction solution.

[0384] Polymer A-8 was obtained by carrying out the reaction in the same manner as described in the synthesis method of polymer A-1 for the subsequent purification process. The weight average molecular weight (Mw) of this polymer A-8 was 19,000, and the imide group introduction rate was 0.43. In addition, the imide group concentration U per repeating unit of the polyimide obtained from polymer A-8 was 16.7 wt%.

[0385] Synthesis of Polymer A-9:

[0386] Polymer A-9 was obtained by carrying out the reaction in the same manner as described in the synthesis method of Polymer A-1, except that 105.6 g of an NMP solution of diamine oligomer W-6 was used instead of 101.7 g of an NMP solution of diamine oligomer W-2 and 2.4 g of m-TB in the synthesis method of Polymer A-1. The weight average molecular weight (Mw) of Polymer A-9 was 29,000, and the imide group introduction rate was 0.43. In addition, the imide group concentration U per repeating unit of the polyimide obtained from Polymer A-9 was 16.8 wt%.

[0387] Synthesis of Polymer A-10:

[0388] Polymer A-10 was obtained by carrying out the reaction in the same manner as described in the synthesis method of Polymer A-2, except that in the synthesis method of Polymer A-2, 4.6 g of BPADA was used instead of 15.2 g, 2.4 g of HEMA was used instead of 7.9 g, 3.6 g of DCC was used instead of 11.9 g, and 174.4 g of the NMP solution of Diamine Oligomer W-7 was used instead of 111.5 g of the NMP solution of Diamine Oligomer W-1. The weight average molecular weight (Mw) of Polymer A-10 was 40,000, and the imide group introduction rate was 0.88. In addition, the imide group concentration U per repeating unit of the polyimide obtained from Polymer A-10 was 16.8 wt%.

[0389] Synthesis of Polymer A-11:

[0390] Polymer A-11 was obtained by carrying out the reaction in the same manner as described in the synthesis method of Polymer A-3, except that in the synthesis method of Polymer A-3, 4.6 g of BPADA was used instead of 15.2 g, 2.4 g of HEMA was used instead of 7.9 g, 3.6 g of DCC was used instead of 11.9 g, 174.4 g of NMP solution of Diamine Oligomer W-7 was used instead of 111.5 g of NMP solution of Diamine Oligomer W-1, and 2.1 g of methacrylate chloride and 1.4 g of pyridine were used instead of 3.1 g of 2-isocyanatoethyl methacrylate. The weight average molecular weight (Mw) of Polymer A-11 was 36,000, and the imide group introduction rate was 0.88. Also, the imide group concentration U per repeating unit of the polyimide obtained from polymer A-11 was 16.8 wt%.

[0391] Synthesis of Polymer A-12:

[0392] Polymer A-12 was obtained by carrying out the reaction in the same manner as described in the synthesis method of Polymer A-1, except that 12.1 g of ODPA was used instead of 20.9 g of BPADA, and 85.5 g of an NMP solution of diamine oligomer W-8 was used instead of 101.7 g of an NMP solution of diamine oligomer W-2 and 2.4 g of m-TB. The weight average molecular weight (Mw) of Polymer A-12 was 26,000, and the imide group introduction rate was 0.58. In addition, the imide group concentration U per repeating unit of the polyimide obtained from Polymer A-12 was 23.6 wt%.

[0393] Synthesis of Polymer A-13:

[0394] Polymer A-13 was obtained by carrying out the reaction in the same manner as described in the synthesis method of Polymer A-1, except that 17.3 g of 6FDA was used instead of 20.9 g of BPADA, and 113.8 g of an NMP solution of diamine oligomer W-9 was used instead of 101.7 g of an NMP solution of diamine oligomer W-2 and 2.4 g of m-TB in the synthesis method of Polymer A-13. The weight average molecular weight (Mw) of Polymer A-13 was 28,000, and the imide group introduction rate was 0.44. In addition, the imide group concentration U per repeating unit of the polyimide obtained from Polymer A-13 was 17.1 wt%.

[0395] Synthesis of Polymer A-14:

[0396] Polymer A-14 was obtained by carrying out the reaction in the same manner as described in the synthesis method of Polymer A-2, except that in the synthesis method of Polymer A-2 above, 7.7 g of 3,3',4,4'-biphenyltetracarboxylic acid anhydride (BPDA) was used instead of 15.2 g of BPADA, 7.1 g of HEMA was used instead of 7.9 g of HEMA, 10.7 g of DCC was used instead of 11.9 g of DCC, and 150.1 g of an NMP solution of Diamine Oligomer W-4 was used instead of 111.5 g of an NMP solution of Diamine Oligomer W-1. The weight average molecular weight (Mw) of Polymer A-14 was 21,000, and the imide group introduction rate was 0.63. In addition, the imide group concentration U per repeating unit of the polyimide obtained from Polymer A-14 was 19.8 wt%.

[0397] Synthesis of Polymer A-15:

[0398] Polymer A-15 was obtained by carrying out the reaction in the same manner as described in the synthesis method of Polymer A-1, except that in the synthesis method of Polymer A-1, 30.6 g of BPADA was used instead of 20.9 g, 15.9 g of HEMA was used instead of 10.9 g, 9.3 g of pyridine was used instead of 6.4 g, 23.9 g of DCC was used instead of 16.3 g, and 45.0 g of NMP solution of Diamine Oligomer W-6 and 14.7 g of MBAPP were used instead of 101.7 g of NMP solution of Diamine Oligomer W-2 and 2.4 g of m-TB. The weight average molecular weight (Mw) of Polymer A-15 was 28,000, and the imide group introduction rate was 0.16. Also, the imide group concentration U per repeating unit of the polyimide obtained from polymer A-15 was 15.8 wt%.

[0399] Synthesis of Polymer A-16:

[0400] Polymer A-16 was obtained by carrying out the reaction in the same manner as described in the synthesis method of Polymer A-1, except that in the synthesis method of Polymer A-1 above, 20.2 g of BPADA was used instead of 20.9 g, 10.5 g of HEMA was used instead of 10.9 g, 15.8 g of DCC was used instead of 16.3 g, and 70 g of the NMP solution of Diamine Oligomer W-10 was used instead of 101.7 g of the NMP solution of Diamine Oligomer W-2. The weight-average molecular weight (Mw) of Polymer A-16 was 26,000, and the imide group introduction rate was 0.44. In addition, the imide group concentration U per repeating unit of the polyimide obtained from Polymer A-16 was 21.1 wt%.

[0401] Synthesis of Polymer A-17:

[0402] Polymer A-17 was obtained by carrying out the reaction in the same manner as described in the synthesis method of Polymer A-2, except that 13.9 g of glycerol dimethacrylate was used instead of 7.9 g of HEMA in the synthesis method of Polymer A-2. The weight average molecular weight (Mw) of Polymer A-17 was 24,000, and the imide group introduction rate was 0.58. In addition, the imide group concentration U per repeating unit of the polyimide obtained from Polymer A-17 was 20.1 wt%.

[0403] Synthesis of Polymer A-18:

[0404] Polymer A-18 was obtained by carrying out the reaction in the same manner as described in the synthesis method of Polymer A-2, except that 7.8 g of 2-aminoethyl methacrylate was used instead of 7.9 g of HEMA in the synthesis method of Polymer A-2. The weight average molecular weight (Mw) of Polymer A-18 was 24,000, and the imide group introduction rate was 0.58. In addition, the imide group concentration U per repeating unit of the polyimide obtained from Polymer A-18 was 20.1 wt%.

[0405] Synthesis of Polymer A-19:

[0406] Polymer A-19 was obtained by carrying out the reaction in the same manner as described in the synthesis method of Polymer A-2, except that 7.7 g of 2-hydroxybutyl methacrylate (HBMA) and 0.7 g of allyl alcohol were used instead of 7.9 g of HEMA in the synthesis method of Polymer A-2. The weight average molecular weight (Mw) of Polymer A-19 was 24,000, and the imide group introduction rate was 0.58. In addition, the imide group concentration U per repeating unit of the polyimide obtained from Polymer A-19 was 20.1 wt%.

[0407] Synthesis of Polyimide Precursor (Polymer A-20):

[0408] As the acid component, 60.2 g of ODPA was placed in a 1-liter separable flask, and 54.2 g of HEMA and 137.5 g of GBL were added. A reaction mixture was obtained by adding 31.6 g of pyridine while stirring at room temperature. After the exothermic reaction was completed, the mixture was cooled to room temperature and left to stand for an additional 16 hours.

[0409] Next, under ice cooling, a solution of 81.3 g of DCC dissolved in 81.3 g of GBL was added to the reaction mixture over 40 minutes while stirring. Additionally, as a diamine component, a solution of 36.4 g of m-TB dissolved in 109.2 g of GBL was added over 60 minutes while stirring. After stirring at room temperature for 2.5 hours, 15 g of ethyl alcohol was added and stirred for 30 minutes, followed by the addition of 150 g of γ-butyrolactone and stirring at 50°C for 0.5 hours. The precipitate formed in the reaction mixture was removed by filtration to obtain the reaction solution.

[0410] The obtained reaction solution was added to 2,700 g of ethyl alcohol to produce a precipitate consisting of a crude polymer. The resulting crude polymer was filtered and collected, and dissolved in 1,000 g of γ-butyrolactone to obtain a crude polymer solution. The obtained crude polymer solution was applied to an anion exchange resin ("Amberlist" manufactured by Organo Co., Ltd. TM A polymer solution was obtained by purification using

[15] . The obtained polymer solution was added dropwise to 8000 g of water to precipitate the polymer, and the obtained precipitate was filtered and then vacuum dried to obtain a powdered polymer A-20. The weight average molecular weight (Mw) of this polymer A-20 was 19,000, and the imide group introduction rate was 0. In addition, the imide group concentration U per repeating unit of the polyimide obtained from polymer A-20 was 28.8 wt%.

[0411] Synthesis of Polyimide Precursor (Polymer A-21):

[0412] Polymer A-21 was obtained by carrying out the reaction in the same manner as described in the synthesis method of Polymer A-20, except that 63.3 g of BAPP was used instead of 36.4 g of m-TB in the synthesis method of Polymer A-20. The weight average molecular weight (Mw) of Polymer A-21 was 21,000, and the imide group introduction rate was 0. In addition, the imide group concentration U per repeating unit of the polyimide obtained from Polymer A-21 was 20.5 wt%.

[0413] Synthesis of Polyimide Precursor (Polymer A-22):

[0414] Polymer A-22 was obtained by carrying out the reaction in the same manner as described in the synthesis method of Polymer A-20, except that 58.8 g of BPDA was used instead of 62.0 g of ODPA, and 34.3 g of 4,4'-diaminodiphenyl ether (DADPE) was used instead of 36.4 g of m-TB in the synthesis method of Polymer A-20. The weight average molecular weight (Mw) of Polymer A-22 was 22,000, and the imide group introduction rate was 0. In addition, the imide group concentration U per repeating unit of the polyimide obtained from Polymer A-22 was 30.5 wt%.

[0415] Synthesis of Polyimide Precursor (Polymer A-23):

[0416] Polymer A-23 was obtained by carrying out the reaction in the same manner as described in the synthesis method of Polymer A-20, except that 81.3 g of BAPP was used instead of 36.4 g of m-TB in the synthesis method of Polymer A-20. The weight average molecular weight (Mw) of Polymer A-23 was 16,000, and the imide group introduction rate was 0. In addition, the imide group concentration U per repeating unit of the polyimide obtained from Polymer A-23 was 20.5 wt%.

[0417] Synthesis of Polyimide (Polymer A-24):

[0418] 97.7 g of 6FDA as the acid component, 64.1 g of TFMB as the diamine component, and 529.2 g of N-methylpyrrolidone (NMP) as the solvent were added to a 1-liter separable flask equipped with a Dean Stark tube and a condenser, and dissolved while stirring. Additionally, 126.9 g of toluene was added and stirred, after which the temperature was raised to 185 °C under a nitrogen stream. After stirring at 185 °C for 2.5 hours, the toluene in the system and the water produced by imidization were removed over a period of 1.5 hours. Subsequently, the mixture was cooled to room temperature to obtain a polyimide solution.

[0419] The obtained polyimide solution was added to 1,000 g of methyl alcohol to produce a precipitate consisting of an unpurified polymer. The resulting unpurified polymer was filtered and washed again using methyl alcohol. The polymer after washing was vacuum dried at 50 °C to obtain powdered polymer A-24. The weight-average molecular weight (Mw) of this polymer A-24 was 25,000. of polymer A-24 1 H-NMR measurements were performed, and the imide closure rate was confirmed by comparing the peaks derived from the amide bonds with the peaks derived from the aromatic rings of the polyimide. The imide closure rate was 99% or higher. In addition, the imide group concentration U per repeating unit of the polyimide obtained from polymer A-24 was 19.2 wt%.

[0420] <Components (B) ~ (G)>

[0421] Photopolymerization Initiator B1: 3-cyclopentyl-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]propanone-1-(O-acetyloxime) (Trade name: PBG-304, manufactured by Changzhou Jiangxiang Electronics Co., Ltd.)

[0422] Photopolymerization Initiator B2: 1,2-propanedione-3-cyclopentyl-1-[4-(phenylthio)phenyl]-2-(O-benzoyloxime) (Product Name: PBG-305, Manufactured by Changzhou Jiangxiang Electronics Co., Ltd.)

[0423] Photopolymerization Initiator B3: 1-[4-(phenylthio)phenyl]-3-propane-1,2-dione-2-(O-acetyl oxime) (Product Name: PBG-3057, Manufactured by Changzhou Jiangxi Electronics Co., Ltd.)

[0424] Solvent C1: γ-butyrolactone

[0425] Solvent C2: Dimethyl sulfoxide (DMSO)

[0426] Solvent C3: 3-Methoxy-N,N-Dimethylpropanamide

[0427] Silane Coupling Agent D-1: 3-Glycidoxypropyltrimethoxysilane (Manufactured by Shin-Etsu Chemical Co., Ltd.)

[0428] Silane coupling agent D-2: N-phenyl-3-aminopropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd.)

[0429] Silane coupling agent D-3: (3-triethoxysilylpropyl)-tert-butylcarbamate

[0430] Silane Coupling Agent D-4: Ureidopropyltriethoxysilane (Manufactured by Shin-Etsu Chemical Co.)

[0431] Silane coupling agent D-5: X-12-1214A (Trade name manufactured by Shin-Etsu Chemical Co., Ltd.)

[0432] Silane coupling agent D-6: Tris(-trimethoxysilylpropyl)isocyanurate (manufactured by Shin-Etsu Chemical Co., Ltd.)

[0433] Radical polymerizable compound E-1: 1,6-hexanediol dimethacrylate (manufactured by Shinnakamura Chemical Co., Ltd.)

[0434] Radical polymerizable compound E-2: Pentaerythritol tetraacrylate (manufactured by Shinnakamura Chemical Co., Ltd.)

[0435] Radical polymerizable compound E-3: (PO modified) trimethylolpropane triacrylate (manufactured by Shinnakamura Chemical Co., Ltd.)

[0436] Radical polymerizable compound E-4: Dipentaerythritol hexaacrylate (manufactured by Shinnakamura Chemical Co., Ltd.)

[0437] Thermal crosslinking agent F-1: Bismaleimide compound (Manufactured by Daiwa Chemical Industry Co., Ltd., BMI-5100)

[0438] Thermal crosslinking agent F-2: Block isocyanate (Manufactured by Asahi Chemical Co., Ltd., SBB70P)

[0439] Thermal crosslinking agent F-3: Alkoxymethyl compound of the following structure (manufactured by Dito Chemics, CROLIN-318)

[0440] [Chemical Formula 22]

[0441]

[0442] Filler G-1: Spherical Silica (Manufactured by Admatex, K180SP-CY1)

[0443] <Example 1>

[0444] As shown in Table 3, 100 g of polymer A-1 as component (A) and 7 g of photopolymerization initiator B-1 as component (B) were dissolved in a mixed solvent (weight ratio 90:10) consisting of γ-butyrolactone and DMSO as solvent (C) to form a photosensitive resin composition solution. This composition was evaluated by the method described above.

[0445] <Examples 2–37, Comparative Examples 1–9>

[0446] A photosensitive resin composition solution was prepared and evaluated in the same manner as in Example 1, except that the types and amounts of the components were prepared in the ratios listed in Tables 3 to 6. Only in Comparative Example 8, the photosensitive resin composition solution prepared was left to stand at 40°C for 240 hours. Using the photosensitive resin composition after standing, the imidization rate as a photosensitive resin composition layer was measured by the method for measuring the imide structure introduction rate, and the result was 0.45. The characteristics and evaluation results are shown in Tables 3 to 6.

[0447]

[0448]

[0449]

[0450]

[0451]

[0452]

[0453] As is evident from Tables 1 to 6, in the examples, by introducing a polyimide block structure at a specific ratio, it was possible to provide a photosensitive resin composition capable of forming a cured relief pattern with high copper adhesion at high resolution, while having low dielectric properties, low curing shrinkage, and good storage stability, and reduced phase separation during coating. On the other hand, in Comparative Examples 1 to 6, which did not have a polyimide structure, the dielectric loss tangent was high and the residual film rate after curing was low. In Comparative Example 7, in which polyimide was blended with a polyimide precursor having an imide group introduction rate of 0, it was difficult to evaluate the resolution because compatibility was poor and uniform coating could not be achieved. Furthermore, it is thought that the result was a high dielectric loss tangent and low copper adhesion due to phase separation. In Comparative Example 8, which used a partially imidized polyimide precursor, the dielectric loss tangent was low, but it is thought that the film after coating became white and cloudy because it was difficult to control the imidization, resulting in poor resolution. In Comparative Example 9, which used 100% imide polymer, radical polymerizable monomers were required for patterning, and although the residual film rate after curing was high, the dielectric loss tangent was high and the resolution was low. From the above results, insufficient results were obtained in all comparative examples.

[0454] Industrial applicability

[0455] The photosensitive resin composition of the present disclosure can be preferably used in the field of photosensitive materials useful for manufacturing electrical and electronic materials, such as semiconductor devices and multilayer wiring boards.

Claims

Claim 1 A photosensitive resin composition comprising (A) a copolymer resin comprising 100 parts by mass of a polyimide and a polyimide precursor; (B) 0.5 to 30 parts by mass of a photopolymerization initiator; and (C) 100 to 1000 parts by mass of a solvent; wherein the copolymer resin comprising the polyimide and the polyimide precursor has a structure represented by the following general formula (1). (1) In the above formula (1), X1, X2 and X3 are each independently a tetravalent organic group having 6 to 40 carbon atoms, Y1 and Y2 are each independently a divalent organic group having 6 to 40 carbon atoms, n1 is an integer from 2 to 30, n2 and n3 are each independently an integer from 2 to 150, Z3, Z4, Z5 and Z6 are each independently a monovalent organic group, and at least one of Z3, Z4, Z5 and Z6 is a photopolymerizable functional group, and the copolymer resin comprising the polyimide and the polyimide precursor satisfies 0.10 < n2 / (n2 + n3) < 0.90, a photosensitive resin composition. Claim 2 A photosensitive resin composition according to claim 1, wherein the photopolymerizable functional group comprises a structure represented by the following general formula (2). (In Equation (2), R5, R6, and R7 are each independently a hydrogen atom or a monovalent organic group having 1 to 3 carbon atoms, and m1 is an integer from 2 to 10.) Claim 3 A photosensitive resin composition according to claim 1 or 2, wherein n2 / (n2 + n3) satisfies 0.40 < n2 / (n2 + n3) < 0.

90. Claim 4 The photosensitive resin composition according to claim 1 or 2, wherein the copolymer resin comprising (A) polyimide and polyimide precursor does not contain halogen atoms. Claim 5 A photosensitive resin composition according to claim 1 or 2, wherein the polyimide of the polyimide cured film obtained by heating and curing the photosensitive resin composition at 350°C has an imide group concentration U, which is the ratio of the molecular weight of the imide group to the molecular weight of a repeating unit comprising a structure derived from a tetracarboxylic acid dianhydride and a diamine, of 12 wt% to 26 wt%. Claim 6 In claim 1 or 2, X1, X2, and X3 of the copolymer resin comprising the (A) polyimide and the polyimide precursor comprise a structure represented by the following general formula (4), and In formula (4), R8 and R9 are each independently organic groups having 1 to 10 carbon atoms, m2 and m3 are integers selected from 0 to 4, satisfying m2 + m3 ≥ 1, and Z1 is selected from any group consisting of single bonds, organic groups having 1 to 30 carbon atoms, and organic groups containing heteroatoms, * two of which represent bonds to the main chain of the resin, and the other two represent bonds to the side chains in the above general formula (1); also / or, Y1 and / or Y2 comprise a structure represented by the following general formula (7), and A photosensitive resin composition, wherein in formula (7), R8 and R9 are each independently organic groups having 1 to 10 carbon atoms, m2 and m3 are integers selected from 0 to 4, satisfying m2 + m3 ≥ 1, Z1 is selected from the group consisting of single bonds, organic groups having 1 to 30 carbon atoms, and organic groups containing heteroatoms, and * indicates bonding to the main chain of the resin. Claim 7 A photosensitive resin composition according to claim 1 or 2, wherein the copolymer resin comprising (A) the polyimide and the polyimide precursor has a reactive substituent at the resin end that polymerizes by heat or light, which is different from the photopolymerizable functional group included in the repeating unit. Claim 8 A photosensitive resin composition according to claim 1 or 2, further comprising (D) a silane coupling agent. Claim 9 A photosensitive resin composition according to claim 1 or 2, further comprising (E) a radical polymerizable compound. Claim 10 A photosensitive resin composition according to claim 1 or 2, further comprising (F) a thermal crosslinking agent. Claim 11 A photosensitive resin composition according to claim 1 or 2, further comprising (G) a filler. Claim 12 The following processes (1) to (5): (1) a process of applying a photosensitive resin composition described in claim 1 or 2 onto a substrate to form a photosensitive resin layer on the substrate; (2) a process of heating and drying the obtained photosensitive resin layer; (3) a process of exposing the photosensitive resin layer after heating and drying to light; (4) a process of developing the photosensitive resin layer after exposure to light; and (5) a process of heat-treating the photosensitive resin layer after development to form a polyimide cured film; comprising a method for manufacturing a polyimide cured film. Claim 13 A method for manufacturing a cured film obtained by applying a photosensitive resin composition described in claim 1 or 2 onto a substrate, followed by exposure treatment, development treatment, and subsequent heat treatment, wherein the cured film has a dielectric loss tangent of 0.003 to 0.011 measured at 40 GHz using a perturbation-type split cylinder resonance method. Claim 14 A polyimide cured film obtained from the photosensitive resin composition described in claim 1, wherein the dielectric loss tangent at a frequency of 40 GHz by a perturbation-type split-cylinder resonance technique is 0.003 to 0.011, the RFA is 0.81 to 0.93, and the following formula: 85 < RFA / tanδ 40 < 175{In the formula, RFA represents the residual film rate (ratio) after heat setting, and tanδ 40 A polyimide cured film satisfying { represents the dielectric loss tangent at a frequency of 40 GHz by the perturbation-type split cylinder resonance technique.} Claim 15 A method for manufacturing a copolymer resin comprising a polyimide having a structure represented by the following general formula (1) and a polyimide precursor, wherein (1)(In the above formula (1), X1, X2 and X3 are each independently a tetravalent organic group having 6 to 40 carbon atoms, Y1 and Y2 are each independently a divalent organic group having 6 to 40 carbon atoms, n1 is an integer from 2 to 30, n2 and n3 are each independently an integer from 2 to 150, Z3, Z4, Z5 and Z6 are each independently a monovalent organic group, and at least one of Z3, Z4, Z5 and Z6 is a photopolymerizable functional group.) A copolymer resin comprising the above polyimide and polyimide precursor satisfies 0.10 < n2 / (n2 + n3) < 0.90, and the above method comprises the following process: (i) to the first tetracarboxylic acid dianhydride or its acid / substituent adduct, a (1) obtaining a diamine oligomer having repeating units of a polyimide structure by condensing and imidizing a diamine compound; (ii) synthesizing a polyimide-imide precursor portion having a polyimide block portion by condensing the diamine oligomer with a second tetracarboxylic acid dianhydride or its acid / substituent adduct; (iii) synthesizing a polyimide precursor portion by condensing the polyimide-imide precursor portion with a third tetracarboxylic acid dianhydride or its acid / substituent adduct and a second diamine compound, wherein the first tetracarboxylic acid dianhydride, the second tetracarboxylic acid dianhydride, and the third tetracarboxylic acid dianhydride may be the same or different from each other, and at least among the second tetracarboxylic acid dianhydride and the third tetracarboxylic acid dianhydride A method for preparing a copolymer resin, wherein one is in the form of an acid / substituent adduct having a photopolymerizable functional group, and the first diamine compound and the second diamine compound may be the same or different from each other. Claim 16 A method for manufacturing a photosensitive resin composition, wherein the method comprises: manufacturing a copolymer resin comprising a polyimide and a polyimide precursor by the method described in claim 15; and a process of mixing (A) 100 parts by mass of the copolymer resin comprising the polyimide and the polyimide precursor, (B) 0.5 to 30 parts by mass of a photopolymerization initiator, and (C) 100 to 1000 parts by mass of a solvent to obtain a photosensitive resin composition.

Citation Information

Patent Citations

  • Block copolymer, its production, liquid crystal orientation material, liquid crystal orientation film, substrate sandwiched with liquid crystal sandwiched, and liquid crystal display element

    JP1996100061A

  • Highly transparent poly(amic acid-imide) copolymer and positive-type photosensitive resin composition containing the same, and cured film of the composition

    JP2005336243A

  • Method for producing polyimide cured film

    JP2022054415A